A ZnS / MnS heterojunction composite photocatalytic powder, a photocatalytic self-healing anti-corrosion coating, and their preparation methods and applications
Photocatalytic self-healing anti-corrosion coatings were prepared by using ZnS/MnS heterojunction composite photocatalytic powders. This solved the problem of bath corrosion caused by hydrogen ions in the traditional immersion phosphating system, achieving self-healing of the coating and improvement of phosphating film quality, extending equipment life and reducing costs.
Patent Information
- Application Number
- CN202611167628.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-11-06
AI Technical Summary
The presence of hydrogen ions in the bath solution of traditional immersion phosphating systems accelerates corrosion, reduces the thickness of the tank wall, causes localized corrosion defects, and makes the coating prone to aging and peeling, affecting the quality of the phosphating film and equipment safety.
A photocatalytic self-healing anti-corrosion coating was prepared using ZnS/MnS heterojunction composite photocatalytic powder. The coating generates phosphate through photocatalysis to protect the metal substrate and regulate the stability of the phosphating solution and the self-healing properties of the coating.
It effectively extends the service life of the tank, reduces equipment costs, improves the quality of the phosphating film, ensures production stability and safety, and the coating has a self-healing function.
Smart Images

Figure CN123038833A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalyst and metal phosphating technology, specifically relating to a ZnS / MnS heterojunction composite photocatalytic powder, a photocatalytic self-healing anti-corrosion coating, and their preparation methods and applications. Background Technology
[0002] Traditional immersion phosphating systems use highly acidic baths containing a large number of hydrogen ions. The presence of these hydrogen ions not only provides ample reactants for electrochemical corrosion but also readily induces side reactions (competitive electron consumption) at the interface of oxidizing components such as nitrate ions in the bath, leading to an imbalance in the bath environment and further accelerating the corrosion process of the substrate. Long-term corrosion can cause thinning of the bath walls, inducing localized corrosion defects such as pitting and crevice corrosion, significantly shortening equipment lifespan and substantially increasing equipment replacement and maintenance costs. Simultaneously, iron, nickel, and other metal ions dissolved during corrosion continuously enter the phosphating solution, causing an imbalance in the bath composition and a surge in sludge, resulting in quality defects such as pinholes, looseness, and poor adhesion of the phosphating film on the workpiece, severely weakening the protective performance of the phosphating film. Furthermore, bath corrosion also poses safety hazards such as leakage and component breakage, threatening the continuity and stability of production.
[0003] To address the corrosion problem of traditional immersion phosphating systems, existing technologies mainly employ two solutions: First, using corrosion-resistant metal materials such as stainless steel and titanium alloys to prepare the tank and core components. However, the procurement and processing costs of such materials are high, and corrosion and ion leaching problems cannot be completely avoided in the long-term high-temperature and highly acidic phosphating solution environment. Second, lining the inner wall of the tank with anti-corrosion isolation coatings such as rubber and fiberglass. However, these organic coatings are prone to aging, cracking, and peeling under the combined effects of high temperature, alternating acid and alkali conditions, and mechanical scouring of the tank solution. The peeled coating fragments can also contaminate the phosphating solution, causing new product quality problems.
[0004] Therefore, a low-cost and efficient method is needed to overcome / mitigate tank corrosion and improve phosphating quality. Summary of the Invention
[0005] To overcome the shortcomings of existing technologies, this invention provides a ZnS / MnS heterojunction composite photocatalytic powder, a photocatalytic self-healing anti-corrosion coating, its preparation method, and its application. The ZnS / MnS powder prepared by this invention has a heterojunction structure, good dispersibility, and good photocatalytic performance. The photocatalytic self-healing anti-corrosion coating based on ZnS / MnS powder can generate phosphate under light irradiation to effectively protect the metal substrate from corrosion; at the same time, it maintains the stability of the phosphating solution and improves the crystallinity quality of the phosphating film.
[0006] The technical solution adopted by this invention to solve its technical problem is: This invention provides a method for preparing ZnS / MnS heterojunction composite photocatalytic powder, comprising the following steps: The composite metal source, the compound regulating agent and the slow-release sulfur source were dissolved in the compound solvent, the pH was adjusted to 5.0-5.4, and the reaction was carried out hydrothermally to obtain ZnS / MnS heterojunction composite photocatalytic powder. By weight percentage, the composite metal source is 5.0%–7.0%, the slow-release sulfur source is 3.8%–6.0%, the compound regulating agent is 0.28%–0.42%, and the balance is the compound solvent; The composite metal source includes soluble zinc salt and soluble manganese salt, the compound regulatory agent includes nonionic biodispersant and silane-modified precursor, and the slow-release sulfur source includes thioacetamide.
[0007] Furthermore, the soluble zinc salt is zinc acetate dihydrate, and the soluble manganese salt is manganese acetate tetrahydrate.
[0008] Furthermore, the molar ratio of zinc ions to manganese ions in the composite metal source is (6~8):(4~2).
[0009] More preferably, the molar ratio of zinc ions to manganese ions in the composite metal source is 7:3.
[0010] Furthermore, the nonionic dispersant is dodecyl glucoside, and the silane auxiliary is KH-550 aminosilane coupling agent.
[0011] Furthermore, the mass ratio of the nonionic biodispersant to the silane-modified precursor is (2~4):1.
[0012] More preferably, the mass ratio of the nonionic biodispersant to the silane-modified precursor is 3:1.
[0013] Furthermore, the pH was adjusted using an aqueous solution of acetic acid.
[0014] Furthermore, the compounding solvent is deionized water and anhydrous ethanol.
[0015] More preferably, the volume ratio of deionized water to anhydrous ethanol is (7~9):1.
[0016] More preferably, the volume ratio of deionized water to anhydrous ethanol is 9:1.
[0017] Furthermore, the hydrothermal reaction temperature is 140–160℃, and the holding time is 10–12 hours.
[0018] Furthermore, the heating rate of the hydrothermal reaction is 2.5–4 °C.
[0019] Further, after the hydrothermal reaction, the product is cooled, aged, washed, dried, and baked to obtain ZnS / MnS heterojunction composite photocatalytic powder.
[0020] More preferably, the cooling is carried out by allowing the vessel to cool naturally to room temperature.
[0021] More preferably, the aging process is natural static aging for 12 to 15 hours.
[0022] More preferably, the washing process involves alternating between anhydrous ethanol and deionized water.
[0023] More preferably, the drying is vacuum drying, with a temperature of 55-60°C, a time of 9-11 hours, and a vacuum degree of -0.08 to -0.1 MPa.
[0024] More preferably, the drying temperature is 210℃~230℃, the drying time is 2~2.5h, and the atmosphere is nitrogen.
[0025] Further, under stirring conditions, the composite metal source, the compound regulating agent, and the slow-release sulfur source solution were sequentially added to a portion of the compound solvent to adjust the pH to 5.0–5.4. The remaining compound solvent was then added, and a hydrothermal reaction was carried out to obtain ZnS / MnS heterojunction composite photocatalytic powder.
[0026] More preferably, the slow-release sulfur source solution is added dropwise over a period of 2–3 hours.
[0027] The present invention also provides a ZnS / MnS heterojunction composite photocatalytic powder prepared by the above preparation method.
[0028] This invention also provides a photocatalytic self-healing anti-corrosion coating, comprising component A and component B. Component A comprises fluorine-modified phenolic epoxy resin, the aforementioned ZnS / MnS heterojunction composite photocatalytic powder, composite acid-resistant passivating and rust-preventing filler, matching compounding additives, and solvent; component B comprises acid-resistant low-temperature curing agent and solvent; component A and component B are mixed before use. By weight percentage, the photocatalytic self-healing anti-corrosion coating (including component A and component B) contains 34.0%–36.5% fluorinated modified phenolic epoxy resin, 11.5%–13.5% ZnS / MnS heterojunction composite photocatalytic powder, 18.0%–20.0% composite acid-resistant passivating and rust-preventing filler, 4.2%–4.9% matching compounded additives, 12.0%–14.0% acid-resistant low-temperature curing agent, and the balance being solvent.
[0029] Furthermore, the mass ratio of the solvent in component A to the solvent in component B is 7~9:1~3.
[0030] More preferably, the mass ratio of the solvent in component A to the solvent in component B is 8:2.
[0031] Furthermore, the composite acid-resistant passivating and rust-preventing filler includes modified aluminum tripolyphosphate, zinc phosphate, glass flakes, and fumed silica.
[0032] More preferably, the mass ratio of modified aluminum tripolyphosphate, zinc phosphate, glass flakes, and fumed silica is 4~5∶3~4∶3~4∶1.
[0033] More preferably, the mass ratio of modified aluminum tripolyphosphate, zinc phosphate, glass flakes and fumed silica is 5:3:4:1.
[0034] Furthermore, the supporting compounding agents include block polyether dispersants, polysiloxane defoamers, modified acrylic leveling agents, benzotriazole free radical scavengers, and polyamide wax antisettling agents.
[0035] More preferably, the mass ratio of block polyether dispersant, polysiloxane defoamer, modified acrylic leveling agent, benzotriazole free radical scavenger and polyamide wax antisettling agent is 4.0~5.0∶2.0~2.5∶2~2.5∶0.7~0.8∶0.7~0.8.
[0036] More preferably, the mass ratio of block polyether dispersant, polysiloxane defoamer, modified acrylic leveling agent, benzotriazole free radical scavenger and polyamide wax antisettling agent is 4.0:2.0:2.5:0.8:0.7.
[0037] Furthermore, the fluorine content of the fluorinated phenolic epoxy resin is 10-15 wt%.
[0038] More preferably, the fluorine content of the fluorinated phenolic epoxy resin is 15 wt%.
[0039] Furthermore, the acid-resistant low-temperature curing agent is a modified cycloaliphatic amine-phenolic adduct.
[0040] More preferably, the modified cycloaliphatic amine-phenolic adduct has an amine value of 380–420 mg KOH / g and can be completely cured at 50–60°C.
[0041] Furthermore, the solvent is an environmentally friendly high-boiling-point compound solvent.
[0042] More preferably, the environmentally friendly high-boiling-point compound solvent includes divalent ester (DBE), propylene glycol diacetate (PGDA), and propylene glycol methyl ether acetate (PMA).
[0043] More preferably, the mass ratio of divalent ester, propylene glycol diacetate, and propylene glycol methyl ether acetate is 3~4:3~4:3~4.
[0044] More preferably, the mass ratio of divalent ester, propylene glycol diacetate, and propylene glycol methyl ether acetate is 3:4:3.
[0045] The present invention also provides a method for preparing the above-mentioned photocatalytic self-healing anti-corrosion coating, comprising the following steps: Fluorine-modified phenolic epoxy resin, matching compounded additives, and ZnS / MnS heterojunction composite photocatalytic powder were added to a solvent, ground, and then a composite acid-resistant passivating and rust-preventing filler was added to obtain component A. Acid-resistant low-temperature curing agent is added to a solvent to obtain component B.
[0046] This invention also provides a method for preparing a photocatalytic self-healing anti-corrosion coating, comprising the following steps: (1) Grind, clean, and sandblast the metal substrate, apply primer, and let it dry; (2) Apply the first layer of the above-mentioned photocatalytic self-healing anti-corrosion coating, let it dry, and roughen the surface. (3) Apply a second layer of the above photocatalytic self-healing anti-corrosion coating and dry it to obtain a photocatalytic self-healing anti-corrosion coating.
[0047] Further, step (1) sanding is done with coarse sandpaper and fine sandpaper, with coarse sandpaper being 70~80# and fine sandpaper being 120~130#.
[0048] More preferably, the coarse sandpaper is 80# and the fine sandpaper is 120#.
[0049] Further, step (1) cleaning is high-pressure water rinsing, followed by air drying.
[0050] Furthermore, in step (1), the sandblasting is performed at a pressure of 0.50–0.60 MPa, with a single-sided area sandblasting speed of 30–45 s / m. 2 .
[0051] Further, the roughness of the substrate after sandblasting in step (1) is 60-80 μm.
[0052] Further, after sandblasting in step (1), the dust is removed.
[0053] Furthermore, step (1) involves applying one coat of primer.
[0054] Furthermore, the primer in step (1) is a thin phosphating passivation primer with a dry film thickness of 15-20 μm.
[0055] Further, step (1) drying is performed at room temperature for 2-4 hours.
[0056] Furthermore, in step (2), the dry film thickness of the first layer of photocatalytic self-healing anti-corrosion coating is 80-85 μm.
[0057] Further, in step (2), drying involves standing at room temperature for 6-8 hours followed by baking at 55-65°C for 16-20 hours.
[0058] Further, step (2) roughening is done with 300~400# sandpaper.
[0059] Further, step (2) involves cleaning the dust after roughening the surface.
[0060] Furthermore, in step (3), the dry film thickness of the second layer of photocatalytic self-healing anti-corrosion coating is 120-130 μm.
[0061] Further, step (3) drying involves standing at room temperature for 8-10 hours followed by baking at 55-65℃ for 24-30 hours.
[0062] This invention also provides an application of the above-mentioned method for preparing a photocatalytic self-healing anti-corrosion coating in metal corrosion protection. This is particularly relevant for equipment in contact with the phosphating solution during metal phosphating processes, such as phosphating tanks.
[0063] The present invention also provides a phosphating tank, wherein a photocatalytic self-healing anti-corrosion coating is prepared on the inner wall of the phosphating tank according to the above preparation method.
[0064] The present invention also provides a metal phosphating process in which a zinc-manganese phosphating solution is added to the above-mentioned phosphating tank, and the metal workpiece is immersed in the zinc-manganese phosphating solution to generate a zinc-manganese composite phosphating film on the surface of the metal workpiece. The inner wall of the phosphating tank is exposed to light; the zinc-manganese phosphating solution contains citric acid.
[0065] Furthermore, the zinc-manganese phosphating solution is obtained by diluting the mother liquor, which by weight percentage comprises: 43%–47% phosphoric acid, 8.5%–11.0% manganese dihydrogen phosphate, 3.0%–4.2% manganese nitrate, 5.0%–6.5% zinc dihydrogen phosphate, 4.5%–6.0% zinc nitrate, 2.2%–3.2% citric acid, with the remainder being deionized water.
[0066] Furthermore, the preparation method of zinc-manganese phosphating solution includes the following steps: Under stirring conditions, phosphoric acid, manganese dihydrogen phosphate, and manganese nitrate are dissolved in a portion of water in sequence. Then, zinc dihydrogen phosphate and zinc nitrate are dissolved in sequence. Finally, citric acid is added, followed by the remaining water, to obtain a zinc-manganese phosphating solution. The remaining water can be added before use.
[0067] Furthermore, the total acidity of the zinc-manganese phosphating solution is 25-40 points, and the free acidity is 3-6 points.
[0068] Furthermore, the temperature of the zinc-manganese phosphating solution is 80–85°C.
[0069] Furthermore, the soaking time is 8-12 minutes.
[0070] Furthermore, the metal workpiece is a steel workpiece.
[0071] Furthermore, the metal workpiece undergoes degreasing, water washing, rust removal, and neutralization pretreatment.
[0072] Furthermore, the lighting is either natural light or artificial light.
[0073] The ZnS / MnS heterojunction structure constructed in this invention broadens the photoresponse range, significantly improves the separation efficiency of photogenerated electron-hole pairs, and exhibits strong hydrogen ion consumption capacity. By employing a slow-release sulfur source of thioacetamide, a compound additive of dodecyl glucoside and KH-550, and a preparation process involving hydrothermal reaction + natural aging + low-temperature nitrogen heat treatment, the resulting powder exhibits uniform particle size, good dispersibility, and is less prone to agglomeration in coating systems, resulting in long-lasting and stable photocatalytic activity. The photocatalytic powder demonstrates high activity, good stability, and sustained catalytic performance.
[0074] This invention uses a fluorine-modified phenolic epoxy resin with a fluorine content of 15% as the film-forming matrix, combined with a composite acid-resistant passivating and rust-inhibiting filler composed of modified aluminum tripolyphosphate, zinc phosphate, glass flakes, and fumed silica. This filler can withstand the high temperatures, strong acidity, and mechanical erosion during the immersion phosphating process for extended periods. The modified cycloaliphatic amine-phenolic adduct low-temperature curing agent used can fully cure at 50-65℃, adapting to the on-site construction requirements of phosphating tanks. The coating exhibits excellent corrosion resistance, suitable for the harsh working conditions of phosphating tanks.
[0075] This invention utilizes photogenerated electrons generated by a ZnS / MnS heterojunction photocatalytic material under light irradiation to actively reduce and consume hydrogen ions at the coating interface, artificially regulating the interface microenvironment to increase its local pH value. This process disrupts the ionization balance of dihydrogen phosphate in the bath solution, promoting the release of phosphate ions and their combination with zinc / manganese ions. This results in the in-situ deposition of a dense phosphate self-healing film at the coating damage site, automatically filling microcracks and effectively overcoming the problem of traditional coatings failing immediately after damage. It achieves integrated active corrosion protection and photoresponsive self-healing, significantly extending the protective lifespan and regulating the bath solution microenvironment.
[0076] This invention eliminates the need for expensive corrosion-resistant metals such as stainless steel and titanium alloys in the tank construction, significantly reducing initial equipment investment. It effectively extends the tank's lifespan, reduces equipment replacement and maintenance frequency, ensures production continuity and stability, and prevents production safety accidents caused by equipment corrosion and leakage. Furthermore, this invention uses environmentally friendly high-boiling-point compound solvents with a VOC content ≤420g / L, complying with the GB 30981-2020 national standard, making it green and environmentally friendly. The entire process reduces costs and increases efficiency while improving production safety.
[0077] The beneficial effects of this invention are: The ZnS / MnS heterojunction composite photocatalytic powder prepared by this invention has a heterojunction structure, good dispersibility, and good photocatalytic performance; in particular, the molar ratio of zinc to manganese is 7:3, which results in even better performance.
[0078] The photocatalytic self-healing anti-corrosion coating prepared by this invention can effectively regulate the acidity of the phosphating solution and generate phosphates under light irradiation, preventing metal corrosion and protecting the metal substrate. The coating can also self-heal and provide long-term protection to the base substrate. At the same time, it maintains the acidity of the phosphating solution and prevents the precipitation of metal ions from the metal substrate, improves the crystal quality of the phosphating film, and has strong adhesion. The resulting phosphated workpiece has good corrosion resistance. Attached Figure Description
[0079] Figure 1 The XRD patterns are of the ZnS / MnS powders prepared in Examples 3, 4, and 5 of this invention. Figure 2 The XRD patterns are of the ZnS / MnS powders prepared in Comparative Examples 7, 8, and 9 of this invention. Figure 3 These are scanning electron microscope (SEM) images of ZnS / MnS powders prepared in Examples 3, 3, and 6-9 of this invention. Figure 4 Metallographic images of the inner surface of the substrate of the tank after phosphating in Embodiment 3 and Comparative Examples 1, 2, 7, 10, and 11 of the present invention; Figure 5 These are electron microscope images of the workpiece surface after phosphating in Embodiment 3 and Comparative Examples 1-11 of the present invention. Detailed Implementation
[0080] The present invention will be further described below with reference to embodiments.
[0081] The following will clearly and completely describe the concept, specific solutions, and technical effects of the present invention with reference to embodiments, so as to fully understand the purpose, features, and effects of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention. The various technical features in the present invention can be combined interactively without contradicting each other.
[0082] Photocatalytic materials, with their unique photoelectrochemical properties, have shown great potential in the field of metal corrosion protection. When excited by light of a specific wavelength, photocatalytic materials generate photogenerated electron-hole pairs, triggering interfacial redox reactions. When a photocatalytic material coating is applied to the inner wall of the tank, the photogenerated electrons can react with hydrogen ions on the coating surface, effectively reducing the local hydrogen ion concentration and disrupting the ionization equilibrium of dihydrogen phosphate in the tank solution. This causes dihydrogen phosphate to undergo positive ionization and release phosphate ions. After the phosphate ions combine with metal cations such as zinc and manganese in the tank solution, they deposit in situ on the coating surface, forming a dense and uniform phosphate protective film, serving as the first line of defense against corrosion by isolating the acidic tank solution from the substrate.
[0083] This protective process has dynamic self-regulating characteristics: when the surface phosphate film is partially damaged due to the rinsing of the bath solution and friction of materials, the photocatalytic coating exposed at the damaged area will continue to play a role under light, and will redeposit the phosphate film layer in the damaged area through the mechanism of consuming hydrogen ions and promoting the ionization of dihydrogen phosphate, thereby achieving dynamic self-repair of the protective film and maintaining a long-term stable anti-corrosion effect.
[0084] This invention organically combines a photocatalytic functional coating with a traditional immersion phosphating system. Through photocatalysis, it regulates the interfacial hydrogen ion concentration, induces in-situ phosphate deposition, and achieves dynamic self-healing corrosion protection. The immersion phosphating tank corrosion protection technology based on a photocatalytic coating utilizes photocatalysis to regulate the local acid-base environment, forming a dynamically renewing phosphate protective layer in situ. This solves the tank corrosion problem in immersion phosphating systems, extends equipment service life, reduces production and maintenance costs, reduces tank solution contamination, and stabilizes product phosphating quality.
[0085] This invention provides a ZnS / MnS heterojunction composite photocatalytic powder, the raw materials of which include the following components by weight percentage: 5.0%–7.0% industrial-grade composite metal source (purity ≥98.5%), 3.8%–6.0% industrial-grade slow-release sulfur source (purity ≥98.2%), 0.28%–0.42% industrial-grade compound regulating agent (purity ≥99.2%), and pH adjuster, glacial acetic acid dilute aqueous solution added as needed to adjust the pH of the system to 5.0–5.4, with the balance being a compound solvent of industrial-grade deionized water and anhydrous ethanol.
[0086] The composite metal source is composed of zinc acetate dihydrate and manganese acetate tetrahydrate, and the two are used in combination with a metal salt molar ratio of Zn. 2+ Mn 2+ =7:3.
[0087] The slow-release sulfur source is industrial-grade thioacetamide, which replaces conventional sulfur sources such as sodium sulfide and thiourea.
[0088] The compound regulatory agent includes a nonionic biodispersant and a silane-modified precursor; the nonionic dispersant is selected as dodecyl glucoside, and the silane agent is selected as KH-550 aminosilane coupling agent.
[0089] The mass ratio of dodecyl glucoside to KH-550 in the compound regulatory agent is 3:1.
[0090] The pH adjuster is a 5-10% (w / w) dilute aqueous solution of glacial acetic acid.
[0091] This invention provides a method for preparing a ZnS / MnS composite photocatalytic material, comprising the following steps: S101. Place the compound solvent (deionized water: anhydrous ethanol = 9:1, industrial grade) into the reaction vessel, turn on the magnetic stirrer at room temperature, and control the stirring rate at 320-420 r / min. S102. Add 5.0% to 7.0% of industrial-grade composite metal source (based on the total mass of the preset reaction solution) to the solvent in batches, and stir continuously for 35 to 45 minutes until the solid raw materials are completely dissolved; S103. Keeping the stirring constant, add 0.28% to 0.42% (based on the total mass of the preset reaction solution) of industrial-grade compound regulating agent to the solution obtained in step S102, and continue stirring for 20 to 25 minutes until the agent is completely dispersed and dissolved; S104. Keep the stirring state unchanged, prepare the thioacetamide mother liquor separately, and add 3.8% to 6.0% of industrial grade slow-release sulfur source by peristaltic pump at a uniform dripping rate. The total dripping time is 2 to 3 hours. After the dripping is completed, continue stirring for 15 to 20 minutes. S105. While keeping the stirring constant, slowly add a dilute solution of glacial acetic acid dropwise at a rate of 1 drop / second, monitor the pH in real time, and adjust the pH of the solution to be stable between 5.0 and 5.4. S106. Add the total mass of the reaction solution to the preset total mass using the compound solvent, and continue stirring for 5-10 minutes to obtain a homogeneous precursor suspension; S107. Transfer the suspension into a polytetrafluoroethylene-lined hydrothermal reactor and seal it. Place it in an oven and raise the temperature at a rate of 2.5–4 °C / min to 140–160 °C. Maintain the temperature for 10–12 h. After the reaction is complete, allow the reactor to cool naturally to room temperature (20–25 °C). Allow the material in the reactor to stand naturally for 12–15 h. S108. The hydrothermal products are transferred to a centrifuge and centrifuged at 6000-7000 r / min for 10-13 min to collect the precipitate. The product is then washed alternately with anhydrous ethanol and industrial deionized water 4 times each, and centrifuged for 10-12 min after each wash. S109. The washed filter cake is first placed in a vacuum oven at 55-60℃ and dried at a vacuum degree of (-0.08~-0.1) MPa for 9-11 hours; the dried powder is then transferred to a nitrogen-protected tube furnace and heat-treated at 210℃-230℃ for 2-2.5 hours. After cooling, the ZnS / MnS composite photocatalytic powder for use in anti-corrosion coatings for phosphate baths is obtained.
[0092] This invention provides a special corrosion-resistant photocatalytic coating for the inner wall of a phosphating tank. The raw materials, by weight percentage, include: 34.0%–36.5% fluorine-modified phenolic epoxy resin, 11.5%–13.5% of the ZnS / MnS heterojunction composite powder prepared above, 18.0%–20.0% composite acid-resistant passivating and rust-preventing filler, 4.2%–4.9% matching compounding additives, 12.0%–14.0% acid-resistant low-temperature curing agent, and environmentally friendly high-boiling-point compounding solvent to make up to 100%.
[0093] The fluorine-modified phenolic epoxy resin has a fluorine content of 15 wt%. Fluorine-modified phenolic epoxy resin is a modified resin containing fluorocarbon segments and a phenolic skeleton (fluorine content approximately 15%), such as the fluorine-modified phenolic epoxy resin from Hunan Jiashengde Materials Technology Co., Ltd., and the EPICLON™ fluorine-modified special phenolic epoxy series from DIC Corporation of Japan.
[0094] The composite acid-resistant passivating and rust-preventing filler is prepared by mixing modified aluminum tripolyphosphate, zinc phosphate, glass flakes, and fumed silica in a mass ratio of 5:3:4:1. The modified aluminum tripolyphosphate is a titanium / aluminum composite surface-modified aluminum tripolyphosphate, such as Shijiazhuang Xinsheng Chemical APW-2.
[0095] The accompanying compound additives consist of a block polyether dispersant, a polysiloxane defoamer, a modified acrylic leveling agent, a benzotriazole free radical scavenger, and a polyamide wax anti-settling agent, with a mass ratio of 4.0:2.0:2.5:0.8:0.7. The block polyether dispersant is a copolymer containing acidic groups, such as BASF EFKA FA 4620, Ezhou Anjikang Technology ANJEKA 6910, or BYK-9010 from BYK Chemical. The modified acrylic leveling agent is a polyether-modified polyacrylate leveling agent, such as BYK-3560, BYK-358 N, or Haimingsi from BYK Chemical. Deqian Levelol 495.
[0096] The acid-resistant low-temperature curing agent is a modified alicyclic amine-phenolic adduct with an amine value of 380–420 mg KOH / g, which can be completely cured at 50–60°C. The modified alicyclic amine-phenolic adduct is a Mannich base-modified alicyclic amine curing agent, such as Evonik (formerly Air Products) Ancamine 2072 and Cardolite NC-541.
[0097] The environmentally friendly high-boiling-point compound solvent is a mixture of divalent ester (DBE), propylene glycol diacetate (PGDA) and propylene glycol methyl ether acetate (PMA) in a mass ratio of 3:4:3, with a VOC content ≤420g / L, meeting the requirements of GB 30981-2020 standard.
[0098] The present invention also provides a method for preparing and using the above-mentioned anti-corrosion coating for phosphating tanks, comprising the following steps: S201. At room temperature, add 60% of the environmentally friendly high-boiling-point compound solvent to the stirred tank, turn on the stirrer, and control the speed at 300-400 r / min; S202. Add the fluorine-modified phenolic epoxy resin in two batches, stirring continuously for 35-40 minutes until the resin is completely dissolved and there are no gel particles. S203. Keep the stirring rate constant, add all the matching compound additives, and stir for 20-25 minutes to ensure that the additives are evenly dissolved in the liquid. S204. First, add all the ZnS / MnS heterojunction composite powder, increase the speed to 1000-1200 r / min and pre-disperse for 15 min. Then, transfer it to a horizontal sand mill and grind it to a fineness of ≤15 μm to obtain a photocatalytic slurry. After transferring it back to the stirring tank, add the composite acid-resistant passivating and rust-preventing filler in small amounts several times. After the addition is complete, increase the speed to 1200-1400 r / min and disperse at high speed for 30-35 min. S205. Test the fineness and viscosity of the coating (Ford-4 cup, 25℃: 80~100s). Add 20% of the compounded solvent according to the specifications, and stir at low speed for 15~20min to homogenize the system. ("Ford-4 cup, 25℃: 80~100s", "Ford-4 cup": refers to measurement using a Ford-4 viscometer as specified in GB / T 1723-1993 "Determination of Viscosity of Coatings". This is the most commonly used viscosity testing standard in my country's industrial coating production and application, suitable for measuring the viscosity of coatings with a flow time of no more than 150s. "25℃" is the standard test temperature specified by the national standard. Because coating viscosity is extremely sensitive to temperature (viscosity changes by approximately 5%~10% for every 1℃ change in temperature), measurement must be performed under constant temperature conditions to ensure the accuracy and comparability of the results. 80~100s) This is a proprietary process specification for this product. This range of values is the optimal application viscosity range specifically designed for the formulation system and airless spraying process of this phosphate bath anti-corrosion coating: Below 80s: The coating is too thin, prone to sagging during spraying, and the dry film thickness is insufficient, resulting in a decrease in anti-corrosion performance; Above 100s: The coating is too thick, resulting in poor atomization, orange peel and pinholes on the paint film surface, and the spray gun is prone to clogging. This range can simultaneously ensure the storage stability of the coating, the application properties of the spraying, and the density of the final paint film. S206. Filter the mixture through a 300-mesh screen to remove impurities, and then seal and package it to obtain component A. Separately, mix the acid-resistant low-temperature curing agent with the remaining 20% of the compound solvent and stir for 10-15 minutes. Filter the mixture through a 200-mesh screen and then seal and package it to obtain component B. Mix components A and B thoroughly before use. S207. First, use 80# coarse sandpaper to sand the inner surface of the phosphating tank to remove the old coating, loose rust and loose attachments. Then, use 120# sandpaper to sand the surface to smooth the edges and burrs. Rinse thoroughly with high-pressure water and let it dry until there is no free moisture on the surface. S208. Sandblasting is performed using an air pressure of 0.50–0.60 MPa, with a single-sided area sandblasting speed of 30–45 s / m. 2 After the substrate roughness is 60-80μm and dust is removed, apply one coat of epoxy zinc-rich primer (dry film thickness 15-20μm). After drying at room temperature for 2 hours, apply the first coat with a dry film thickness of 80-85μm. After pre-drying at room temperature for 6 hours, bake at 55-65℃ for 16 hours. After the coating is cured, lightly roughen the surface of the coating with 400# sandpaper, clean off the dust, and then apply the second coat. The dry film thickness of the second coat should be 200-215μm, which is the same as the first coat. After coating, let stand at room temperature for 8 hours, then bake at 55-65℃ for 24 hours. After drying and shaping, it can be put into the phosphating tank for use.
[0099] This invention provides a special zinc-manganese phosphating solution mother liquor suitable for use with this coating tank. The raw materials include, by weight percentage: 43%–47% phosphoric acid, 8.5%–11.0% manganese dihydrogen phosphate, 3.0%–4.2% manganese nitrate, 5.0%–6.5% zinc dihydrogen phosphate, 4.5%–6.0% zinc nitrate, 2.2%–3.2% citric acid, and the balance being deionized water.
[0100] The citric acid has a dual function: on the one hand, it acts as a complexation regulator in the phosphating system, stabilizing the ion concentration in the bath and preventing the precipitation of metal salt crystals; on the other hand, it acts as a hole sacrificial agent for the ZnS / MnS photocatalytic system, matching the working mechanism of the photocatalytic powder in the tank wall coating, continuously consuming photogenerated holes, improving the efficiency of the powder in consuming hydrogen ions in the bath that corrode the tank, and providing long-term stability to the phosphating solution.
[0101] This invention provides a matching phosphating solution preparation and steel wire phosphating steps: S301. Under normal temperature conditions, add metered deionized water to the stirred reaction vessel, start low-speed stirring, control the speed at 200-260 r / min, and slowly add phosphoric acid, manganese dihydrogen phosphate and manganese nitrate in sequence, and continue stirring for 25-35 min until all solid salts are completely dissolved. S302. While keeping the stirring constant, add zinc dihydrogen phosphate and zinc nitrate in sequence, stir for 15-20 minutes until the materials are completely dispersed and dissolved, and finally add citric acid. Continue stirring at a constant temperature for 25-30 minutes to prepare a uniform and stable phosphating concentrated mother liquor. S303. Use deionized water to dilute and adjust the concentrated mother liquor, precisely control the tank liquid parameters, control the total acidity to 25-40 points and the free acidity to 3-6 points, and let it stand for 30 minutes to stabilize before use. S304. After the coating on the inner wall of the phosphating tank has been completely cured, inject the prepared working solution into the phosphating tank, heat it at a uniform rate to 80-85℃, and keep it at a stable temperature for 10 minutes. S305. After degreasing, washing, rust removal and neutralization pretreatment, steel workpieces are completely immersed in phosphating bath and phosphated at a constant temperature for 8 to 12 minutes, resulting in a uniform and dense zinc-manganese composite phosphating film on the workpiece surface. S306. During long-term use of the bath solution, relying on the ZnS / MnS heterojunction photocatalytic powder loaded on the bath wall, and using citric acid as a photocatalytic sacrificial agent, phosphate in-situ deposition is induced by photogenerated electrons consuming interfacial hydrogen ions under natural light or indoor lighting conditions. This self-healing deposition process has intelligent self-limiting characteristics: on the one hand, the interfacial micro-electric field characteristics of the ZnS / MnS heterojunction cause photogenerated electrons to undergo a reduction reaction with H+ at the coating interface; on the other hand, as the self-healing phosphate film thickens, its dense structure blocks light transmission, thereby automatically inhibiting the further progress of the photocatalytic reaction, so that the film thickness reaches a dynamic equilibrium, avoiding scaling and peeling problems caused by unlimited thickness, and effectively preventing the bath solution from corroding the bath body.
[0102] The fluorinated phenolic epoxy resin used in the following examples and comparative examples is a modified resin containing fluorocarbon segments and a phenolic skeleton (fluorine content approximately 15%), namely DIC Corporation's EPICLON™ fluorinated special phenolic epoxy series; the modified aluminum tripolyphosphate is titanium / aluminum composite surface-modified aluminum tripolyphosphate, namely Shijiazhuang Xinsheng Chemical APW-2; the block polyether dispersant is a polyether copolymer containing acidic groups, namely BASF EFKA FA 4620; the modified alicyclic amine-phenolic adduct is an adduct containing alicyclic amine and phenolic Mannich base structure, namely Evonik (formerly Air Products) Ancamine 2072. The phosphating tank is made of low-carbon steel.
[0103] Example 1 A ZnS / MnS heterojunction composite photocatalytic powder comprises the following components by weight percentage: 7.0% industrial-grade composite metal source (purity ≥98.5%), 6.0% industrial-grade slow-release sulfur source (purity ≥98.2%), 0.42% industrial-grade compound regulating agent (purity ≥99.2%), pH adjuster (dilute aqueous solution of glacial acetic acid added as needed to adjust the pH of the system to 5.4), and the balance being a compound solvent of industrial-grade deionized water and anhydrous ethanol.
[0104] The composite metal source is composed of zinc acetate dihydrate and manganese acetate tetrahydrate, with a metal salt molar ratio of Zn... 2+ Mn2 + =7:3; the slow-release sulfur source is industrial-grade thioacetamide; the compound regulating agent includes dodecyl glucoside and KH-550 aminosilane coupling agent, with a mass ratio of 3:1; the pH adjuster is a dilute aqueous solution of glacial acetic acid (mass concentration 5%); the compound solvent contains deionized water: anhydrous ethanol = 9:1.
[0105] The preparation method of the above-mentioned ZnS / MnS heterojunction composite photocatalytic powder includes the following steps: S101. Place the compounded solvent in the reaction vessel, turn on the magnetic stirrer at room temperature, and control the stirring rate at 420 r / min; S102. Add 7.0% industrial-grade composite metal source (based on a preset total mass of 1000g of reaction solution) to the solvent in batches, and stir continuously for 45 minutes until the solid raw materials are completely dissolved; S103. Keeping the stirring state unchanged, add 0.42% (based on the total mass of the preset reaction solution) of industrial-grade compound regulating agent to the solution obtained in step S102, and continue stirring for 25 minutes until the agent is completely dispersed and dissolved; S104. Keeping the stirring state unchanged, prepare the thioacetamide mother liquor (mass concentration 15%) using the compound solvent alone, and add 6.0% industrial grade slow-release sulfur source by uniform dripping using a peristaltic pump. The entire dripping process takes 3 hours, and stirring continues for 20 minutes after the dripping is completed. S105. Keep stirring constant and slowly add a dilute aqueous solution of glacial acetic acid dropwise at a rate of 1 drop / second. Monitor the pH in real time with a pH meter and adjust the pH of the solution to be stable at 5.4. S106. Add the compound solvent to the preset total mass of the reaction solution, and continue stirring for 10 min to obtain a homogeneous precursor suspension; S107. Transfer the suspension into a polytetrafluoroethylene-lined hydrothermal reactor and seal it. Place it in an oven and heat it to 160°C at a rate of 4°C / min. Maintain the temperature for 12 hours. After the reaction is complete, allow the reactor to cool naturally to room temperature (20-25°C). Let the material in the reactor stand naturally for 15 hours to age. S108. The hydrothermal product was transferred to a centrifuge and centrifuged at 7000 r / min for 13 min to collect the precipitate. It was then washed alternately with anhydrous ethanol and industrial deionized water 4 times each, and centrifuged for 12 min after each wash. S109. The washed filter cake is first placed in a vacuum oven at 60℃ and dried at a vacuum of -0.1MPa for 11 hours. The dried powder is then transferred to a nitrogen-protected tube furnace and heat-treated at 230℃ for 2.5 hours. After cooling, ZnS / MnS heterojunction composite photocatalytic powder for use in anti-corrosion coatings for phosphating tanks is obtained.
[0106] A special corrosion-resistant photocatalytic coating for the inner wall of a phosphating tank, comprising the following raw materials by weight percentage: 36.5% fluorine-modified phenolic epoxy resin (fluorine content 15%), 13.5% of the ZnS / MnS heterojunction composite photocatalytic powder prepared above, 20.0% composite acid-resistant passivating and rust-preventing filler, 4.9% matching compounding additives, 14.0% acid-resistant low-temperature curing agent, and environmentally friendly high-boiling-point compounding solvent to make up to 100%.
[0107] The composite acid-resistant passivating and rust-preventing filler is prepared by mixing modified aluminum tripolyphosphate, zinc phosphate, glass flakes, and fumed silica in a mass ratio of 5:3:4:1. The supporting compounding additives consist of block polyether dispersant, polysiloxane defoamer, modified acrylic leveling agent, benzotriazole free radical scavenger, and polyamide wax anti-settling agent, with a mass ratio of 4.0:2.0:2.5:0.8:0.7. The acid-resistant low-temperature curing agent is a modified alicyclic amine-phenolic adduct with an amine value of 420 mgKOH / g, which can be completely cured at 50-60℃. The environmentally friendly high-boiling-point compounding solvent is a compound of divalent ester (DBE), propylene glycol diacetate (PGDA), and propylene glycol methyl ether acetate (PMA) in a mass ratio of 3:4:3, with a VOC content ≤420g / L, meeting the requirements of GB30981-2020 standard.
[0108] The preparation and application methods of the above-mentioned corrosion-resistant photocatalytic coating for the inner wall of the phosphating tank include the following steps: S201. At room temperature, add 60wt% of environmentally friendly high-boiling-point compound solvent to the stirred tank, start stirring, and control the speed at 400r / min; S202. Add the fluorine-modified phenolic epoxy resin in two batches, stirring continuously for 40 minutes until the resin is completely dissolved and there are no gel particles. S203. Keep the stirring rate constant, add all the matching compound additives, stir for 25 minutes to make the additives evenly dissolved in the liquid; S204. First, add all the ZnS / MnS heterojunction composite powder, increase the speed to 1200 r / min and pre-disperse for 15 min, then transfer to a horizontal sand mill and grind until the fineness is ≤15 μm to obtain photocatalytic slurry. After transferring back to the stirring tank, add the composite acid-resistant passivating and rust-preventing filler in small amounts and multiple times. After the addition is completed, increase the speed to 1400 r / min and disperse at high speed for 35 min. S205. Test the fineness and viscosity of the coating (Ford cup 4, 25℃: 100s). Add 20% of the compounded solvent according to the index and stir at low speed for 20 minutes to mix the system. S206. Filter the mixture through a 300-mesh filter to remove impurities, and then seal and package it to obtain component A. Separately, mix the acid-resistant low-temperature curing agent with the remaining 20% of the compound solvent and stir for 15 minutes. Filter the mixture through a 200-mesh filter and then seal and package it to obtain component B. Mix components A and B thoroughly before use. S207. First, use 80# coarse sandpaper to sand the inner surface of the phosphating tank to remove the old coating, floating rust and loose attachments. Then, use 120# sandpaper to sand the surface to smooth the edges and burrs. Rinse thoroughly with high-pressure water and let it dry until there is no free moisture on the surface. S208. Sandblasting is performed using 0.60MPa air pressure, with a single-sided area sandblasting speed of 45s / m. 2 After the substrate roughness is 80μm and dust is removed, an epoxy zinc-rich primer (dry film thickness 20μm) is applied. After drying at room temperature for 2 hours, the first coating is applied with a dry film thickness of 85μm. After pre-drying at room temperature for 6 hours, it is baked at 65℃ for 16 hours. After the coating is cured, the surface of the coating is lightly roughened by hand with 400# sandpaper. After cleaning the dust, a second coating is applied. The dry film thickness of the second coating, combined with the dry film thickness of the first coating, is 215μm. After coating, the substrate is left to stand at room temperature for 8 hours, and then baked at 65℃ for 24 hours. After drying and shaping, it can be put into the phosphating tank for use.
[0109] A special zinc-manganese phosphating solution mother liquor, the raw materials of which by weight percentage include: 47% phosphoric acid, 11.0% manganese dihydrogen phosphate, 4.2% manganese nitrate, 6.5% zinc dihydrogen phosphate, 6.0% zinc nitrate, 3.2% citric acid, and the balance being deionized water.
[0110] The citric acid has a dual function: on the one hand, it acts as a complexation regulator in the phosphating system, stabilizing the ion concentration in the bath and preventing the precipitation of metal salt crystals; on the other hand, it acts as a hole sacrificial agent for the ZnS / MnS photocatalytic system, matching the working mechanism of the photocatalytic powder in the tank wall coating, continuously consuming photogenerated holes, improving the efficiency of the powder in consuming hydrogen ions in the bath that corrode the tank, and providing long-term stability to the phosphating solution.
[0111] The preparation method of the above-mentioned special zinc-manganese phosphating solution and the phosphating method of steel wire include the following steps: S301. Under normal temperature conditions, add metered deionized water to the stirred reaction vessel, start low-speed stirring, control the speed at 260 r / min, and slowly add phosphoric acid, manganese dihydrogen phosphate and manganese nitrate in sequence, and continue stirring for 35 min until all solid salts are completely dissolved. S302. Keeping the stirring state unchanged, add zinc dihydrogen phosphate and zinc nitrate in sequence, stir for 20 minutes until the materials are completely dispersed and dissolved, and finally add citric acid, continue to stir at a constant temperature for 30 minutes to prepare a uniform and stable phosphating concentrated mother liquor; S303. Use deionized water to dilute and adjust the concentrated mother liquor, precisely control the tank liquid parameters, control the total acidity to 40 points and the free acidity to 6 points, and let it stand for 30 minutes to stabilize before use. S304. After the coating on the inner wall of the phosphating tank has been completely cured, inject the prepared working solution into the phosphating tank, heat it to 85°C at a uniform rate, and keep it at a stable temperature for 10 minutes. S305. After degreasing, washing, rust removal and neutralization pretreatment, steel workpieces are completely immersed in phosphating bath and phosphated at a constant temperature for 12 minutes, resulting in a uniform and dense zinc-manganese composite phosphating film on the workpiece surface. S306. During long-term use of the bath solution, relying on the ZnS / MnS heterojunction photocatalytic powder loaded on the bath wall, and using citric acid as the photocatalytic sacrificial agent, under a constant light source (controlling the irradiance to 500W / m²), 2 Under these conditions, phosphate deposition is induced in situ by consuming interfacial hydrogen ions through photogenerated electrons. This self-healing deposition process possesses intelligent self-limiting characteristics: on the one hand, the interfacial micro-electric field characteristics of the ZnS / MnS heterojunction cause photogenerated electrons to undergo a reduction reaction with H+ at the coating interface; on the other hand, as the self-healing phosphate film thickens, its dense structure blocks light transmission, thereby automatically inhibiting the further progress of the photocatalytic reaction, achieving a dynamic equilibrium in film thickness, avoiding scaling and peeling problems caused by unlimited thickness, and effectively preventing the bath solution from corroding the tank.
[0112] Example 2 A ZnS / MnS heterojunction composite photocatalytic powder comprises the following components by weight percentage: 5.0% industrial-grade composite metal source (purity ≥98.5%), 3.8% industrial-grade slow-release sulfur source (purity ≥98.2%), 0.28% industrial-grade compound regulating agent (purity ≥99.2%), pH adjuster (dilute aqueous solution of glacial acetic acid added as needed to adjust the pH of the system to 5.0), and the balance being a compound solvent of industrial-grade deionized water and anhydrous ethanol.
[0113] The composite metal source is composed of zinc acetate dihydrate and manganese acetate tetrahydrate, with a metal salt molar ratio of Zn... 2+ Mn 2 + =7:3; the slow-release sulfur source is industrial-grade thioacetamide; the compound regulating agent includes dodecyl glucoside and KH-550 aminosilane coupling agent, with a mass ratio of 3:1; the pH adjuster is a dilute aqueous solution of glacial acetic acid (mass concentration 5%); the compound solvent contains deionized water: anhydrous ethanol = 9:1.
[0114] The preparation method of the above-mentioned ZnS / MnS heterojunction composite photocatalytic powder includes the following steps: S101. Place the compound solvent in the reaction vessel, turn on the magnetic stirrer at room temperature, and control the stirring rate at 320 r / min; S102. Add 5.0% industrial-grade composite metal source (based on a preset total mass of 1000g of reaction solution) to the solvent in batches, and stir continuously for 35 minutes until the solid raw materials are completely dissolved; S103. Keeping the stirring constant, add 0.28% (based on the total mass of the preset reaction solution) of industrial-grade compound regulating agent to the solution obtained in step S102, and continue stirring for 20 minutes until the agent is completely dispersed and dissolved; S104. Keeping the stirring state unchanged, prepare the thioacetamide mother liquor (mass concentration 15%) using the compound solvent alone, and add 3.8% industrial grade slow-release sulfur source by uniform dripping using a peristaltic pump. The entire dripping process takes 2 hours, and stirring continues for 15 minutes after the dripping is completed. S105. Keep stirring constant and slowly add a dilute aqueous solution of glacial acetic acid dropwise at a rate of 1 drop / second. Monitor the pH in real time with a pH meter and adjust the pH of the solution to be stable at 5.0. S106. Add the compound solvent to the preset total mass of the reaction solution, and continue stirring for 5 minutes to obtain a homogeneous precursor suspension; S107. Transfer the suspension into a polytetrafluoroethylene-lined hydrothermal reactor and seal it. Place it in an oven and raise the temperature to 140℃ at a rate of 2.5℃ / min. Maintain the temperature for 10 hours. After the reaction is complete, allow the reactor to cool naturally to room temperature (20-25℃). Allow the material in the reactor to stand naturally for 12 hours to age. S108. The hydrothermal product was transferred to a centrifuge and centrifuged at 6000 r / min for 10 min to collect the precipitate. It was then washed alternately with anhydrous ethanol and industrial deionized water 4 times each, and centrifuged for 10 min after each wash. S109. The washed filter cake is first placed in a vacuum oven at 55℃ and dried at a vacuum degree of -0.08MPa for 9 hours; the dried powder is then transferred to a nitrogen-protected tube furnace and heat-treated at 210℃ for 2 hours. After cooling, ZnS / MnS heterojunction composite photocatalytic powder for use in anti-corrosion coatings for phosphating tanks is obtained.
[0115] A special corrosion-resistant photocatalytic coating for the inner wall of a phosphating tank, comprising the following raw materials by weight percentage: 34.0% fluorine-modified phenolic epoxy resin (fluorine content 15%), 11.5% of the ZnS / MnS heterojunction composite photocatalytic powder prepared above, 18.0% composite acid-resistant passivating and rust-preventing filler, 4.2% matching compounding additives, 12.0% acid-resistant low-temperature curing agent, and environmentally friendly high-boiling-point compounding solvent to make up to 100%.
[0116] The composite acid-resistant passivating and rust-preventing filler is prepared by mixing modified aluminum tripolyphosphate, zinc phosphate, glass flakes, and fumed silica in a mass ratio of 5:3:4:1. The supporting compounding additives consist of block polyether dispersant, polysiloxane defoamer, modified acrylic leveling agent, benzotriazole free radical scavenger, and polyamide wax anti-settling agent, with a mass ratio of 4.0:2.0:2.5:0.8:0.7. The acid-resistant low-temperature curing agent is a modified alicyclic amine-phenolic adduct with an amine value of 380 mgKOH / g, which can be completely cured at 50-60℃. The environmentally friendly high-boiling-point compounding solvent is a compound of divalent ester (DBE), propylene glycol diacetate (PGDA), and propylene glycol methyl ether acetate (PMA) in a mass ratio of 3:4:3, with a VOC content ≤420g / L, meeting the requirements of GB30981-2020 standard.
[0117] The preparation and application methods of the above-mentioned corrosion-resistant photocatalytic coating for the inner wall of the phosphating tank include the following steps: S201. At room temperature, add 60wt% of environmentally friendly high-boiling-point compound solvent to the stirred tank, start stirring, and control the speed at 300r / min; S202. Add the fluorine-modified phenolic epoxy resin in two batches, stirring continuously for 35 minutes until the resin is completely dissolved and there are no gel particles. S203. Keep the stirring rate constant, add all the matching compound additives, stir for 20 minutes to make the additives evenly dissolved in the liquid; S204. First, add all the ZnS / MnS heterojunction composite powder, increase the speed to 1000 r / min for pre-dispersion for 15 min, then transfer it to a horizontal sand mill to grind until the fineness is ≤15 μm to obtain photocatalytic slurry. After transferring it back to the stirring tank, add the composite acid-resistant passivating and rust-preventing filler in small amounts and multiple times. After the addition is completed, increase the speed to 1200 r / min and disperse at high speed for 30 min. S205. Test the fineness and viscosity of the coating (Ford cup 4, 25℃: 80s). Add 20% of the compounded solvent according to the index and stir at low speed for 15 minutes to mix the system. S206. Filter the mixture through a 300-mesh filter to remove impurities, and then package it in a sealed container to obtain component A. Separately, mix the acid-resistant low-temperature curing agent with the remaining 20% of the compound solvent and stir for 10 minutes. Filter the mixture through a 200-mesh filter and then package it in a sealed container to obtain component B. Mix components A and B thoroughly before use. S207. First, use 80# coarse sandpaper to sand the inner surface of the phosphating tank to remove the old coating, floating rust and loose attachments. Then, use 120# sandpaper to sand the surface to smooth the edges and burrs. Rinse thoroughly with high-pressure water and let it dry until there is no free moisture on the surface. S208. Sandblasting is performed using 0.50MPa air pressure, with a single-sided area sandblasting speed of 30s / m. 2After the substrate roughness is 60μm and dust is removed, a thin phosphating passivation primer (dry film thickness 15μm) is applied. After drying at room temperature for 2 hours, the first coating is applied with a dry film thickness of 80μm. After pre-drying at room temperature for 6 hours, it is baked at 55℃ for 16 hours. After the coating is cured, the surface of the coating is lightly roughened by hand with 400# sandpaper. After cleaning the dust, a second coating is applied. The dry film thickness of the second coating is combined with the dry film thickness of the first coating to make the overall dry film thickness 200μm. After the coating is completed, it is left to stand at room temperature for 8 hours, and then baked at 55℃ for 24 hours. After drying and shaping, it can be put into the phosphating tank for use.
[0118] A special zinc-manganese phosphating solution mother liquor, the raw materials of which by weight percentage include: 43% phosphoric acid, 8.5% manganese dihydrogen phosphate, 3.0% manganese nitrate, 5.0% zinc dihydrogen phosphate, 4.5% zinc nitrate, 2.2% citric acid, and the balance being deionized water.
[0119] The citric acid has a dual function: on the one hand, it acts as a complexation regulator in the phosphating system, stabilizing the ion concentration in the bath and preventing the precipitation of metal salt crystals; on the other hand, it acts as a hole sacrificial agent for the ZnS / MnS photocatalytic system, matching the working mechanism of the photocatalytic powder in the tank wall coating, continuously consuming photogenerated holes, improving the efficiency of the powder in consuming hydrogen ions in the bath that corrode the tank, and providing long-term stability to the phosphating solution.
[0120] The preparation method of the above-mentioned special zinc-manganese phosphating solution and the phosphating method of steel wire include the following steps: S301. Under normal temperature conditions, add metered deionized water to the stirred reaction vessel, start low-speed stirring, control the speed at 200 r / min, and slowly add phosphoric acid, manganese dihydrogen phosphate and manganese nitrate in sequence, and continue stirring for 25 min until all solid salts are completely dissolved. S302. Keeping the stirring state unchanged, add zinc dihydrogen phosphate and zinc nitrate in sequence, stir for 15 minutes until the materials are completely dispersed and dissolved, and finally add citric acid, continue to stir at a constant temperature for 25 minutes to prepare a uniform and stable phosphating concentrated mother liquor; S303. Use deionized water to dilute and adjust the concentrated mother liquor, precisely control the tank liquid parameters, control the total acidity to 25 points and the free acidity to 3 points, and let it stand for 30 minutes to stabilize before use. S304. After the coating on the inner wall of the phosphating tank has been completely cured, inject the prepared working solution into the phosphating tank, heat it to 80°C at a uniform rate, and keep it at a stable temperature for 10 minutes. S305. After degreasing, washing, rust removal and neutralization pretreatment, steel workpieces are completely immersed in phosphating bath and phosphated at a constant temperature for 8 minutes, resulting in a uniform and dense zinc-manganese composite phosphating film on the workpiece surface. S306. During long-term use of the bath solution, relying on the ZnS / MnS heterojunction photocatalytic powder loaded on the bath wall, and using citric acid as the photocatalytic sacrificial agent, under a constant light source (controlling the irradiance to 500W / m²), 2 Under these conditions, phosphate deposition is induced in situ by consuming interfacial hydrogen ions through photogenerated electrons. This self-healing deposition process possesses intelligent self-limiting characteristics: on the one hand, the interfacial micro-electric field characteristics of the ZnS / MnS heterojunction cause photogenerated electrons to undergo a reduction reaction with H+ at the coating interface; on the other hand, as the self-healing phosphate film thickens, its dense structure blocks light transmission, thereby automatically inhibiting the further progress of the photocatalytic reaction, achieving a dynamic equilibrium in film thickness, avoiding scaling and peeling problems caused by unlimited thickness, and effectively preventing the bath solution from corroding the tank.
[0121] Example 3 A ZnS / MnS heterojunction composite photocatalytic powder comprises the following components by weight percentage: 6.0% industrial-grade composite metal source (purity ≥98.5%), 4.9% industrial-grade slow-release sulfur source (purity ≥98.2%), 0.35% industrial-grade compound regulating agent (purity ≥99.2%), pH adjuster (dilute aqueous solution of glacial acetic acid added as needed to adjust the pH of the system to 5.2), and the balance being a compound solvent of industrial-grade deionized water and anhydrous ethanol.
[0122] The composite metal source is composed of zinc acetate dihydrate and manganese acetate tetrahydrate, with a metal salt molar ratio of Zn... 2+ Mn 2 + =7:3; the slow-release sulfur source is industrial-grade thioacetamide; the compound regulating agent includes dodecyl glucoside and KH-550 aminosilane coupling agent, with a mass ratio of 3:1; the pH adjuster is a dilute aqueous solution of glacial acetic acid (mass concentration 5%); the compound solvent contains deionized water: anhydrous ethanol = 9:1.
[0123] The preparation method of the above-mentioned ZnS / MnS heterojunction composite photocatalytic powder includes the following steps: S101. Place the compound solvent in the reaction vessel, turn on the magnetic stirrer at room temperature, and control the stirring rate at 370 r / min; S102. Add 6.0% industrial-grade composite metal source (based on a preset total mass of 1000g of reaction solution) to the solvent in batches, and stir continuously for 40 minutes until the solid raw materials are completely dissolved; S103. Keeping the stirring constant, add 0.35% (based on the total mass of the preset reaction solution) of industrial-grade compound regulating agent to the solution obtained in step S102, and continue stirring for 22.5 min until the agent is completely dispersed and dissolved; S104. Keeping the stirring state unchanged, prepare the thioacetamide mother liquor (mass concentration 15%) using the compound solvent alone, and add 4.9% industrial grade slow-release sulfur source by uniform dripping using a peristaltic pump. The total dripping time is 2.5h, and stirring is continued for 17.5min after the dripping is completed. S105. Keep stirring constant and slowly add a dilute aqueous solution of glacial acetic acid dropwise at a rate of 1 drop / second. Monitor the pH in real time with a pH meter and adjust the pH of the solution to be stable at 5.2. S106. Add the mixed solvent to the preset total mass of the reaction solution, and continue stirring for 7.5 min to obtain a homogeneous precursor suspension; S107. Transfer the suspension into a polytetrafluoroethylene-lined hydrothermal reactor and seal it. Place it in an oven and raise the temperature to 150℃ at a rate of 3.25℃ / min. Maintain the temperature for 11 hours. After the reaction is complete, allow the reactor to cool naturally to room temperature (20-25℃). Allow the material in the reactor to stand naturally for 13.5 hours to age. S108. The hydrothermal product was transferred to a centrifuge and centrifuged at 6500 r / min for 11.5 min to collect the precipitate. It was then washed alternately with anhydrous ethanol and industrial deionized water 4 times each, and centrifuged for 11 min after each wash. S109. The washed filter cake is first placed in a vacuum oven at 57.5℃ and dried at a vacuum of -0.09MPa for 10 hours; the dried powder is then transferred to a nitrogen-protected tube furnace and heat-treated at 220℃ for 2.25 hours. After cooling, the ZnS / MnS heterojunction composite photocatalytic powder for use in anti-corrosion coatings for phosphating tanks is obtained.
[0124] A special corrosion-resistant photocatalytic coating for the inner wall of a phosphating tank, comprising the following raw materials by weight percentage: 35.25% fluorine-modified phenolic epoxy resin (fluorine content 15%), 12.5% of the ZnS / MnS heterojunction composite photocatalytic powder prepared above, 19.0% composite acid-resistant passivating and rust-preventing filler, 4.55% matching compounding additives, 13.0% acid-resistant low-temperature curing agent, and environmentally friendly high-boiling-point compounding solvent to make up to 100%.
[0125] The composite acid-resistant passivating and rust-preventing filler is prepared by mixing modified aluminum tripolyphosphate, zinc phosphate, glass flakes, and fumed silica in a mass ratio of 5:3:4:1. The supporting compounding additives consist of block polyether dispersant, polysiloxane defoamer, modified acrylic leveling agent, benzotriazole free radical scavenger, and polyamide wax anti-settling agent, with a mass ratio of 4.0:2.0:2.5:0.8:0.7. The acid-resistant low-temperature curing agent is a modified alicyclic amine-phenolic adduct with an amine value of 400 mg KOH / g, which can be completely cured at 50-60℃. The environmentally friendly high-boiling-point compounding solvent is a compound of divalent ester (DBE), propylene glycol diacetate (PGDA), and propylene glycol methyl ether acetate (PMA) in a mass ratio of 3:4:3, with a VOC content ≤420 g / L, meeting the requirements of GB30981-2020 standard.
[0126] The preparation and application methods of the above-mentioned corrosion-resistant photocatalytic coating for the inner wall of the phosphating tank include the following steps: S201. At room temperature, add 60wt% of environmentally friendly high-boiling-point compound solvent to the stirred tank, start stirring, and control the speed at 350r / min; S202. Add the fluorine-modified phenolic epoxy resin in two batches, stirring continuously for 37.5 minutes until the resin is completely dissolved and there are no gel particles. S203. Keep the stirring rate constant, add all the matching compound additives, stir for 22.5 minutes to make the additives evenly dissolved in the liquid; S204. First, add all the ZnS / MnS heterojunction composite powder, increase the speed to 1100 r / min for pre-dispersion for 15 min, then transfer it to a horizontal sand mill to grind to a fineness ≤15 μm to obtain photocatalytic slurry. After transferring it back to the mixing tank, add the composite acid-resistant passivating and rust-preventing filler in small amounts several times. After the addition is complete, increase the speed to 1300 r / min and disperse at high speed for 32.5 min. S205. Test the fineness and viscosity of the coating (Ford cup 4, 25℃: 90s). Add 20% of the compounded solvent according to the index and stir at low speed for 17.5min to mix the system. S206. Filter the mixture through a 300-mesh filter to remove impurities, and then package it in a sealed container to obtain component A. Separately, mix the acid-resistant low-temperature curing agent with the remaining 20% of the compound solvent and stir for 12.5 minutes. Filter the mixture through a 200-mesh filter and then package it in a sealed container to obtain component B. Mix components A and B thoroughly before use. S207. First, use 80# coarse sandpaper to sand the inner surface of the phosphating tank to remove the old coating, floating rust and loose attachments. Then, use 120# sandpaper to sand the surface to smooth the edges and burrs. Rinse thoroughly with high-pressure water and let it dry until there is no free moisture on the surface. S208. Sandblasting is performed using 0.55MPa air pressure, with a single-sided area sandblasting speed of 37.5s / m. 2After the substrate roughness is 70μm and dust is removed, a thin phosphating passivation primer (dry film thickness 17.5μm) is applied. After drying at room temperature for 2 hours, the first coating is applied, with a dry film thickness of 82.5μm. After pre-drying at room temperature for 6 hours, it is baked at 60℃ for 16 hours. After the coating is cured, the surface is lightly roughened by hand with 400# sandpaper. After cleaning the dust, a second coating is applied, with the second dry film thickness combined with the first dry film thickness, resulting in a total dry film thickness of 207.5μm. After coating, the substrate is left to stand at room temperature for 8 hours, and then baked at 60℃ for 24 hours. After drying and shaping, it can be used in the phosphating tank.
[0127] A special zinc-manganese phosphating solution mother liquor, the raw materials of which by weight percentage include: 45% phosphoric acid, 9.75% manganese dihydrogen phosphate, 3.6% manganese nitrate, 5.75% zinc dihydrogen phosphate, 5.25% zinc nitrate, 2.7% citric acid, and the balance being deionized water.
[0128] The citric acid has a dual function: on the one hand, it acts as a complexation regulator in the phosphating system, stabilizing the ion concentration in the bath and preventing the precipitation of metal salt crystals; on the other hand, it acts as a hole sacrificial agent for the ZnS / MnS photocatalytic system, matching the working mechanism of the photocatalytic powder in the tank wall coating, continuously consuming photogenerated holes, improving the efficiency of the powder in consuming hydrogen ions in the bath that corrode the tank, and providing long-term stability to the phosphating solution.
[0129] The preparation method of the above-mentioned special zinc-manganese phosphating solution and the phosphating method of steel wire include the following steps: S301. Under normal temperature conditions, add metered deionized water to the stirred reaction vessel, start low-speed stirring, control the speed at 230 r / min, and slowly add phosphoric acid, manganese dihydrogen phosphate and manganese nitrate in sequence, and continue stirring for 30 min until all solid salts are completely dissolved. S302. While keeping the stirring constant, add zinc dihydrogen phosphate and zinc nitrate in sequence, stir for 17.5 min until the materials are completely dispersed and dissolved, and finally add citric acid, continue stirring at a constant temperature for 27.5 min to prepare a uniform and stable phosphating concentrated mother liquor; S303. Use deionized water to dilute and adjust the concentrated mother liquor, precisely control the tank liquid parameters, control the total acidity to 35 points and the free acidity to 4.5 points, and let it stand for 30 minutes to stabilize before use. S304. After the coating on the inner wall of the phosphating tank has been completely cured, inject the prepared working solution into the phosphating tank, heat it to 82.5℃ at a uniform rate, and keep it at a stable temperature for 10 minutes. S305. After degreasing, washing, rust removal and neutralization pretreatment, steel workpieces are completely immersed in phosphating bath and phosphated at a constant temperature for 10 minutes, resulting in a uniform and dense zinc-manganese composite phosphating film on the workpiece surface. S306. During long-term use of the bath solution, relying on the ZnS / MnS heterojunction photocatalytic powder loaded on the bath wall, and using citric acid as the photocatalytic sacrificial agent, under a constant light source (controlling the irradiance to 500W / m²), 2 Under these conditions, phosphate deposition is induced in situ by consuming interfacial hydrogen ions through photogenerated electrons. This self-healing deposition process possesses intelligent self-limiting characteristics: on the one hand, the interfacial micro-electric field characteristics of the ZnS / MnS heterojunction cause photogenerated electrons to undergo a reduction reaction with H+ at the coating interface; on the other hand, as the self-healing phosphate film thickens, its dense structure blocks light transmission, thereby automatically inhibiting the further progress of the photocatalytic reaction, achieving a dynamic equilibrium in film thickness, avoiding scaling and peeling problems caused by unlimited thickness, and effectively preventing the bath solution from corroding the tank.
[0130] Example 4 A ZnS / MnS heterojunction composite photocatalytic powder comprises the following components by weight percentage: 7.0% industrial-grade composite metal source (purity ≥98.5%), 6.0% industrial-grade slow-release sulfur source (purity ≥98.2%), 0.42% industrial-grade compound regulating agent (purity ≥99.2%), pH adjuster (dilute aqueous solution of glacial acetic acid added as needed to adjust the pH of the system to 5.4), and the balance being a compound solvent of industrial-grade deionized water and anhydrous ethanol.
[0131] The composite metal source is composed of zinc acetate dihydrate and manganese acetate tetrahydrate, with a metal salt molar ratio of Zn... 2+ Mn 2 + =7:3; the slow-release sulfur source is industrial-grade thioacetamide; the compound regulating agent includes dodecyl glucoside and KH-550 aminosilane coupling agent, with a mass ratio of 3:1; the pH adjuster is a dilute aqueous solution of glacial acetic acid (mass concentration 5%); the compound solvent contains deionized water: anhydrous ethanol = 9:1.
[0132] The preparation method of the above-mentioned ZnS / MnS heterojunction composite photocatalytic powder includes the following steps: S101. Place the compounded solvent in the reaction vessel, turn on the magnetic stirrer at room temperature, and control the stirring rate at 420 r / min; S102. Add 7.0% industrial-grade composite metal source (based on a preset total mass of 1000g of reaction solution) to the solvent in batches, and stir continuously for 45 minutes until the solid raw materials are completely dissolved; S103. Keeping the stirring state unchanged, add 0.42% (based on the total mass of the preset reaction solution) of industrial-grade compound regulating agent to the solution obtained in step S102, and continue stirring for 25 minutes until the agent is completely dispersed and dissolved; S104. Keeping the stirring state unchanged, prepare the thioacetamide mother liquor (mass concentration 15%) using the compound solvent alone, and add 6.0% industrial grade slow-release sulfur source by uniform dripping using a peristaltic pump. The entire dripping process takes 3 hours, and stirring continues for 20 minutes after the dripping is completed. S105. Keep stirring constant and slowly add a dilute aqueous solution of glacial acetic acid dropwise at a rate of 1 drop / second. Monitor the pH in real time with a pH meter and adjust the pH of the solution to be stable at 5.4. S106. Add the compound solvent to the preset total mass of the reaction solution, and continue stirring for 10 min to obtain a homogeneous precursor suspension; S107. Transfer the suspension into a polytetrafluoroethylene-lined hydrothermal reactor and seal it. Place it in an oven and heat it to 160°C at a rate of 4°C / min. Maintain the temperature for 12 hours. After the reaction is complete, allow the reactor to cool naturally to room temperature (20-25°C). Let the material in the reactor stand naturally for 15 hours to age. S108. The hydrothermal product was transferred to a centrifuge and centrifuged at 7000 r / min for 13 min to collect the precipitate. It was then washed alternately with anhydrous ethanol and industrial deionized water 4 times each, and centrifuged for 12 min after each wash. S109. The washed filter cake is first placed in a vacuum oven at 60℃ and dried at a vacuum of -0.1MPa for 11 hours. The dried powder is then transferred to a nitrogen-protected tube furnace and heat-treated at 230℃ for 2.5 hours. After cooling, ZnS / MnS heterojunction composite photocatalytic powder for use in anti-corrosion coatings for phosphating tanks is obtained.
[0133] A special corrosion-resistant photocatalytic coating for the inner wall of a phosphating tank, comprising the following raw materials by weight percentage: 36.5% fluorine-modified phenolic epoxy resin (fluorine content 15%), 13.5% of the ZnS / MnS heterojunction photocatalytic composite powder prepared above, 20.0% composite acid-resistant passivating and rust-preventing filler, 4.9% matching compound additives, 14.0% acid-resistant low-temperature curing agent, and environmentally friendly high-boiling-point compound solvent to make up to 100%.
[0134] The composite acid-resistant passivating and rust-preventing filler is prepared by mixing modified aluminum tripolyphosphate, zinc phosphate, glass flakes, and fumed silica in a mass ratio of 5:3:4:1. The supporting compounding additives consist of block polyether dispersant, polysiloxane defoamer, modified acrylic leveling agent, benzotriazole free radical scavenger, and polyamide wax anti-settling agent, with a mass ratio of 4.0:2.0:2.5:0.8:0.7. The acid-resistant low-temperature curing agent is a modified alicyclic amine-phenolic adduct with an amine value of 420 mgKOH / g, which can be completely cured at 50-60℃. The environmentally friendly high-boiling-point compounding solvent is a compound of divalent ester (DBE), propylene glycol diacetate (PGDA), and propylene glycol methyl ether acetate (PMA) in a mass ratio of 3:4:3, with a VOC content ≤420g / L, meeting the requirements of GB30981-2020 standard.
[0135] The preparation and application methods of the above-mentioned corrosion-resistant photocatalytic coating for the inner wall of the phosphating tank include the following steps: S201. At room temperature, add 60wt% of environmentally friendly high-boiling-point compound solvent to the stirred tank, start stirring, and control the speed at 400r / min; S202. Add the fluorine-modified phenolic epoxy resin in two batches, stirring continuously for 40 minutes until the resin is completely dissolved and there are no gel particles. S203. Keep the stirring rate constant, add all the matching compound additives, stir for 25 minutes to make the additives evenly dissolved in the liquid; S204. First, add all the ZnS / MnS heterojunction composite powder, increase the speed to 1200 r / min and pre-disperse for 15 min, then transfer to a horizontal sand mill and grind until the fineness is ≤15 μm to obtain photocatalytic slurry. After transferring back to the stirring tank, add the composite acid-resistant passivating and rust-preventing filler in small amounts and multiple times. After the addition is completed, increase the speed to 1400 r / min and disperse at high speed for 35 min. S205. Test the fineness and viscosity of the coating (Ford cup 4, 25℃: 100s). Add 20% of the compounded solvent according to the index and stir at low speed for 20 minutes to mix the system. S206. Filter the mixture through a 300-mesh filter to remove impurities, and then seal and package it to obtain component A. Separately, mix the acid-resistant low-temperature curing agent with the remaining 20% of the compound solvent and stir for 15 minutes. Filter the mixture through a 200-mesh filter and then seal and package it to obtain component B. Mix components A and B thoroughly before use. S207. First, use 80# coarse sandpaper to sand the inner surface of the phosphating tank to remove the old coating, floating rust and loose attachments. Then, use 120# sandpaper to sand the surface to smooth the edges and burrs. Rinse thoroughly with high-pressure water and let it dry until there is no free moisture on the surface. S208. Sandblasting is performed using 0.60MPa air pressure, with a single-sided area sandblasting speed of 45s / m. 2 After the substrate roughness is 80μm and dust is removed, a thin phosphating passivation primer (dry film thickness 20μm) is applied. After drying at room temperature for 2 hours, the first coating is applied, with a dry film thickness of 85μm. After pre-drying at room temperature for 6 hours, it is baked at 65℃ for 16 hours. After the coating is cured, the surface of the coating is lightly roughened by hand with 400# sandpaper. After cleaning the dust, a second coating is applied, with the dry film thickness of the second coating combined with the first dry film thickness, resulting in a total dry film thickness of 215μm. After coating, the substrate is left to stand at room temperature for 8 hours, and then baked at 65℃ for 24 hours. After drying and shaping, it can be put into the phosphating tank for use.
[0136] A special zinc-manganese phosphating solution mother liquor, the raw materials of which by weight percentage include: 43% phosphoric acid, 8.5% manganese dihydrogen phosphate, 3.0% manganese nitrate, 5.0% zinc dihydrogen phosphate, 4.5% zinc nitrate, 2.2% citric acid, and the balance being deionized water.
[0137] The citric acid has a dual function: on the one hand, it acts as a complexation regulator in the phosphating system, stabilizing the ion concentration in the bath and preventing the precipitation of metal salt crystals; on the other hand, it acts as a hole sacrificial agent for the ZnS / MnS photocatalytic system, matching the working mechanism of the photocatalytic powder in the tank wall coating, continuously consuming photogenerated holes, improving the efficiency of the powder in consuming hydrogen ions in the bath that corrode the tank, and providing long-term stability to the phosphating solution.
[0138] The preparation method of the above-mentioned special zinc-manganese phosphating solution and the phosphating method of steel wire include the following steps: S301. Under normal temperature conditions, add metered deionized water to the stirred reaction vessel, start low-speed stirring, control the speed at 200 r / min, and slowly add phosphoric acid, manganese dihydrogen phosphate and manganese nitrate in sequence, and continue stirring for 25 min until all solid salts are completely dissolved. S302. Keeping the stirring state unchanged, add zinc dihydrogen phosphate and zinc nitrate in sequence, stir for 15 minutes until the materials are completely dispersed and dissolved, and finally add citric acid, continue to stir at a constant temperature for 25 minutes to prepare a uniform and stable phosphating concentrated mother liquor; S303. Use deionized water to dilute and adjust the concentrated mother liquor, precisely control the tank liquid parameters, control the total acidity to 25 points and the free acidity to 3 points, and let it stand for 30 minutes to stabilize before use. S304. After the coating on the inner wall of the phosphating tank has been completely cured, inject the prepared working solution into the phosphating tank, heat it to 80°C at a uniform rate, and keep it at a stable temperature for 10 minutes. S305. After degreasing, washing, rust removal and neutralization pretreatment, steel workpieces are completely immersed in phosphating bath and phosphated at a constant temperature for 8 minutes, resulting in a uniform and dense zinc-manganese composite phosphating film on the workpiece surface. S306. During long-term use of the bath solution, relying on the ZnS / MnS heterojunction photocatalytic powder loaded on the bath wall, and using citric acid as the photocatalytic sacrificial agent, under a constant light source (controlling the irradiance to 500W / m²), 2 Under these conditions, phosphate deposition is induced in situ by consuming interfacial hydrogen ions through photogenerated electrons. This self-healing deposition process possesses intelligent self-limiting characteristics: on the one hand, the interfacial micro-electric field characteristics of the ZnS / MnS heterojunction cause photogenerated electrons to undergo a reduction reaction with H+ at the coating interface; on the other hand, as the self-healing phosphate film thickens, its dense structure blocks light transmission, thereby automatically inhibiting the further progress of the photocatalytic reaction, achieving a dynamic equilibrium in film thickness, avoiding scaling and peeling problems caused by unlimited thickness, and effectively preventing the bath solution from corroding the tank.
[0139] Example 5 A ZnS / MnS heterojunction composite photocatalytic powder comprises the following components by weight percentage: 5.0% industrial-grade composite metal source (purity ≥98.5%), 3.8% industrial-grade slow-release sulfur source (purity ≥98.2%), 0.28% industrial-grade compound regulating agent (purity ≥99.2%), pH adjuster (dilute aqueous solution of glacial acetic acid added as needed to adjust the pH of the system to 5.0), and the balance being a compound solvent of industrial-grade deionized water and anhydrous ethanol.
[0140] The composite metal source is composed of zinc acetate dihydrate and manganese acetate tetrahydrate, with a metal salt molar ratio of Zn... 2+ Mn 2 + =7:3; the slow-release sulfur source is industrial-grade thioacetamide; the compound regulating agent includes dodecyl glucoside and KH-550 aminosilane coupling agent, with a mass ratio of 3:1; the pH adjuster is a dilute aqueous solution of glacial acetic acid (mass concentration 5%); the compound solvent contains deionized water: anhydrous ethanol = 9:1.
[0141] The preparation method of the above-mentioned ZnS / MnS heterojunction composite photocatalytic powder includes the following steps: S101. Place the compound solvent in the reaction vessel, turn on the magnetic stirrer at room temperature, and control the stirring rate at 320 r / min; S102. Add 5.0% industrial-grade composite metal source (based on a preset total mass of 1000g of reaction solution) to the solvent in batches, and stir continuously for 35 minutes until the solid raw materials are completely dissolved; S103. Keeping the stirring constant, add 0.28% (based on the total mass of the preset reaction solution) of industrial-grade compound regulating agent to the solution obtained in step S102, and continue stirring for 20 minutes until the agent is completely dispersed and dissolved; S104. Keeping the stirring state unchanged, prepare the thioacetamide mother liquor (mass concentration 15%) using the compound solvent alone, and add 3.8% industrial grade slow-release sulfur source by uniform dripping using a peristaltic pump. The entire dripping process takes 2 hours, and stirring continues for 15 minutes after the dripping is completed. S105. Keep stirring constant and slowly add a dilute aqueous solution of glacial acetic acid dropwise at a rate of 1 drop / second. Monitor the pH in real time with a pH meter and adjust the pH of the solution to be stable at 5.0. S106. Add the compound solvent to the preset total mass of the reaction solution, and continue stirring for 5 minutes to obtain a homogeneous precursor suspension; S107. Transfer the suspension into a polytetrafluoroethylene-lined hydrothermal reactor and seal it. Place it in an oven and raise the temperature to 140℃ at a rate of 2.5℃ / min. Maintain the temperature for 10 hours. After the reaction is complete, allow the reactor to cool naturally to room temperature (20-25℃). Allow the material in the reactor to stand naturally for 12 hours to age. S108. The hydrothermal product was transferred to a centrifuge and centrifuged at 6000 r / min for 10 min to collect the precipitate. It was then washed alternately with anhydrous ethanol and industrial deionized water 4 times each, and centrifuged for 10 min after each wash. S109. The washed filter cake is first placed in a vacuum oven at 55℃ and dried at a vacuum degree of -0.08MPa for 9 hours; the dried powder is then transferred to a nitrogen-protected tube furnace and heat-treated at 210℃ for 2 hours. After cooling, ZnS / MnS heterojunction composite photocatalytic powder for use in anti-corrosion coatings for phosphating tanks is obtained.
[0142] A special corrosion-resistant photocatalytic coating for the inner wall of a phosphating tank, comprising the following raw materials by weight percentage: 34.0% fluorine-modified phenolic epoxy resin (fluorine content 15%), 11.5% of the ZnS / MnS heterojunction composite photocatalytic powder prepared above, 18.0% composite acid-resistant passivating and rust-preventing filler, 4.2% matching compounding additives, 12.0% acid-resistant low-temperature curing agent, and environmentally friendly high-boiling-point compounding solvent to make up to 100%.
[0143] The composite acid-resistant passivating and rust-preventing filler is prepared by mixing modified aluminum tripolyphosphate, zinc phosphate, glass flakes, and fumed silica in a mass ratio of 5:3:4:1. The supporting compounding additives consist of block polyether dispersant, polysiloxane defoamer, modified acrylic leveling agent, benzotriazole free radical scavenger, and polyamide wax anti-settling agent, with a mass ratio of 4.0:2.0:2.5:0.8:0.7. The acid-resistant low-temperature curing agent is a modified alicyclic amine-phenolic adduct with an amine value of 380 mgKOH / g, which can be completely cured at 50-60℃. The environmentally friendly high-boiling-point compounding solvent is a compound of divalent ester (DBE), propylene glycol diacetate (PGDA), and propylene glycol methyl ether acetate (PMA) in a mass ratio of 3:4:3, with a VOC content ≤420g / L, meeting the requirements of GB30981-2020 standard.
[0144] The preparation and application methods of the above-mentioned corrosion-resistant photocatalytic coating for the inner wall of the phosphating tank include the following steps: S201. At room temperature, add 60wt% of environmentally friendly high-boiling-point compound solvent to the stirred tank, start stirring, and control the speed at 300r / min; S202. Add the fluorine-modified phenolic epoxy resin in two batches, stirring continuously for 35 minutes until the resin is completely dissolved and there are no gel particles. S203. Keep the stirring rate constant, add all the matching compound additives, stir for 20 minutes to make the additives evenly dissolved in the liquid; S204. First, add all the ZnS / MnS heterojunction composite powder, increase the speed to 1000 r / min for pre-dispersion for 15 min, then transfer it to a horizontal sand mill to grind until the fineness is ≤15 μm to obtain photocatalytic slurry. After transferring it back to the stirring tank, add the composite acid-resistant passivating and rust-preventing filler in small amounts and multiple times. After the addition is completed, increase the speed to 1200 r / min and disperse at high speed for 30 min. S205. Test the fineness and viscosity of the coating (Ford cup 4, 25℃: 80s). Add 20% of the compounded solvent according to the index and stir at low speed for 15 minutes to mix the system. S206. Filter the mixture through a 300-mesh filter to remove impurities, and then package it in a sealed container to obtain component A. Separately, mix the acid-resistant low-temperature curing agent with the remaining 20% of the compound solvent and stir for 10 minutes. Filter the mixture through a 200-mesh filter and then package it in a sealed container to obtain component B. Mix components A and B thoroughly before use. S207. First, use 80# coarse sandpaper to sand the inner surface of the phosphating tank to remove the old coating, floating rust and loose attachments. Then, use 120# sandpaper to sand the surface to smooth the edges and burrs. Rinse thoroughly with high-pressure water and let it dry until there is no free moisture on the surface. S208. Sandblasting is performed using 0.50MPa air pressure, with a single-sided area sandblasting speed of 30s / m. 2 After the substrate roughness is 60μm and dust is removed, a thin phosphating passivation primer (dry film thickness 15μm) is applied. After drying at room temperature for 2 hours, the first coating is applied with a dry film thickness of 80μm. After pre-drying at room temperature for 6 hours, it is baked at 55℃ for 16 hours. After the coating is cured, the surface of the coating is lightly roughened by hand with 400# sandpaper. After cleaning the dust, a second coating is applied. The dry film thickness of the second coating is combined with the dry film thickness of the first coating to make the overall dry film thickness 200μm. After the coating is completed, it is left to stand at room temperature for 8 hours, and then baked at 55℃ for 24 hours. After drying and shaping, it can be put into the phosphating tank for use.
[0145] A special zinc-manganese phosphating solution mother liquor, the raw materials of which by weight percentage include: 47% phosphoric acid, 11.0% manganese dihydrogen phosphate, 4.2% manganese nitrate, 6.5% zinc dihydrogen phosphate, 6.0% zinc nitrate, 3.2% citric acid, and the balance being deionized water.
[0146] The citric acid has a dual function: on the one hand, it acts as a complexation regulator in the phosphating system, stabilizing the ion concentration in the bath and preventing the precipitation of metal salt crystals; on the other hand, it acts as a hole sacrificial agent for the ZnS / MnS photocatalytic system, matching the working mechanism of the photocatalytic powder in the tank wall coating, continuously consuming photogenerated holes, improving the efficiency of the powder in consuming hydrogen ions in the bath that corrode the tank, and providing long-term stability to the phosphating solution.
[0147] The preparation method of the above-mentioned special zinc-manganese phosphating solution and the phosphating method of steel wire include the following steps: S301. Under normal temperature conditions, add metered deionized water to the stirred reaction vessel, start low-speed stirring, control the speed at 260 r / min, and slowly add phosphoric acid, manganese dihydrogen phosphate and manganese nitrate in sequence, and continue stirring for 35 min until all solid salts are completely dissolved. S302. Keeping the stirring state unchanged, add zinc dihydrogen phosphate and zinc nitrate in sequence, stir for 20 minutes until the materials are completely dispersed and dissolved, and finally add citric acid, continue to stir at a constant temperature for 30 minutes to prepare a uniform and stable phosphating concentrated mother liquor; S303. Use deionized water to dilute and adjust the concentrated mother liquor, precisely control the tank liquid parameters, control the total acidity to 40 points and the free acidity to 6 points, and let it stand for 30 minutes to stabilize before use. S304. After the coating on the inner wall of the phosphating tank has been completely cured, inject the prepared working solution into the phosphating tank, heat it to 85°C at a uniform rate, and keep it at a stable temperature for 10 minutes. S305. After degreasing, washing, rust removal and neutralization pretreatment, steel workpieces are completely immersed in phosphating bath and phosphated at a constant temperature for 12 minutes, resulting in a uniform and dense zinc-manganese composite phosphating film on the workpiece surface. S306. During long-term use of the bath solution, relying on the ZnS / MnS heterojunction photocatalytic powder loaded on the bath wall, and using citric acid as the photocatalytic sacrificial agent, under a constant light source (controlling the irradiance to 500W / m²), 2 Under these conditions, phosphate deposition is induced in situ by consuming interfacial hydrogen ions through photogenerated electrons. This self-healing deposition process possesses intelligent self-limiting characteristics: on the one hand, the interfacial micro-electric field characteristics of the ZnS / MnS heterojunction cause photogenerated electrons to undergo a reduction reaction with H+ at the coating interface; on the other hand, as the self-healing phosphate film thickens, its dense structure blocks light transmission, thereby automatically inhibiting the further progress of the photocatalytic reaction, achieving a dynamic equilibrium in film thickness, avoiding scaling and peeling problems caused by unlimited thickness, and effectively preventing the bath solution from corroding the tank.
[0148] Comparative Example 1 Instead of preparing ZnS / MnS powder, the coating raw material ratio is changed to: 35.25% fluorine-modified phenolic epoxy resin (fluorine content 15%), 19.0% composite acid-resistant passivating and rust-inhibiting filler, 4.55% matching compounded additives, 13.0% acid-resistant low-temperature curing agent, and environmentally friendly high-boiling-point compounded solvent to bring the total to 100%. The addition of ZnS / MnS powder is omitted, while the types and ratios of other fillers and additives remain unchanged. All other steps are the same as in Example 3.
[0149] Comparative Example 2 The ZnS / MnS powder synthesis process, coating preparation steps, sandblasting parameters, dry film thickness, and the formulation and application method of the matching phosphating solution are completely consistent with those in Example 3. Only the composite acid-resistant passivating and rust-inhibiting filler in the coating formulation is adjusted: the zinc phosphate component in the original formulation is removed, and the filler is made solely from modified aluminum tripolyphosphate, glass flakes, and fumed silica in a mass ratio of 5:4:1 (i.e., maintaining the relative proportions of the other three components unchanged). The total filler content remains unchanged as a percentage of the total weight of the coating at 19.0%. All other operating parameters remain unchanged.
[0150] Comparative Example 3 The ZnS / MnS powder raw material ratio, stirring speed, feeding ratio, pH control (5.2), washing and drying, and tube furnace heat treatment parameters all follow those of Example 3; only the S107 hydrothermal process is modified: the heating rate is increased to 100℃ at 3.25℃ / min, the temperature is held constant for 11 hours, and then cooled and aged for 13.5 hours. The other steps before and after the hydrothermal process remain unchanged. All other steps are consistent with those of Example 3.
[0151] Comparative Example 4 The ZnS / MnS powder raw material ratio and synthesis process parameters all followed those in Example 3; the coating formulation, preparation process, sandblasting parameters, dry film thickness, and the formulation and application method of the matching phosphating solution were also completely consistent with Example 3. Only the molar ratio of the metal salts in the composite metal source was adjusted: Zn 2+ Mn 2+ The molar ratio was adjusted from 7:3 to 9:1. All other operating parameters remained unchanged.
[0152] Comparative Example 5 The ZnS / MnS powder raw material ratio and synthesis process parameters all followed those in Example 3; the coating formulation, preparation process, sandblasting parameters, dry film thickness, and matching phosphating solution formulation and usage method were all completely consistent with Example 3. Only the molar ratio of metal salts in the composite metal source was adjusted: Zn 2+ Mn 2+ The molar ratio was adjusted from 7:3 to 1:1. All other operating parameters remained unchanged.
[0153] Comparative Example 6 In the ZnS / MnS powder raw material formulation, 4.9% of the industrial-grade slow-release sulfur source (thioacetamide) was replaced with an equal mass of industrial-grade sodium sulfide nonahydrate (purity ≥98.2%). The amount and ratio of the composite metal source, compound regulating agent, pH adjuster, and solvent system remained unchanged.
[0154] Synthesis process adjustments: In step S104, a separate sodium sulfide aqueous solution mother liquor (10% by mass) was prepared, and 4.9% industrial-grade slow-release sulfur source was added dropwise using a peristaltic pump at a uniform rate. The entire dropwise addition process took 2.5 hours, and stirring continued for 17.5 minutes after the addition was completed. The parameters for all other steps S101~S103 and S105~S109 were the same as in Example 3. All other steps were consistent with Example 3.
[0155] Comparative Example 7 The compound regulating agent components were completely removed from the ZnS / MnS powder raw material formulation, and no dodecyl glucoside and KH-550 aminosilane coupling agent were added; the amount and ratio of the composite metal source, slow-release sulfur source, pH adjuster, and solvent system were consistent with those in Example 3.
[0156] Synthesis process adjustment: The original S103 addition step was deleted. After the metal salt in S102 is completely dissolved, it directly enters the S104 sulfur source dropwise addition step. The corresponding stirring time and subsequent process parameters remain unchanged. All other steps are the same as in Example 3.
[0157] Comparative Example 8 The proportions of all other raw materials and the synthesis process parameters for ZnS / MnS powder all follow those in Example 3; only the components of the compounding control agent are adjusted: KH-550 aminosilane coupling agent is removed, and only dodecyl glucoside is retained. Its dosage is consistent with the effective proportion of dodecyl glucoside in the compounding agent in Example 3 (0.263wt%, corresponding to 3 / 4 of the original 0.35wt% compounding agent).
[0158] Synthesis process adjustment: In step S103, only dodecyl glucoside was added, and the mixture was stirred continuously for 22.5 min until completely dispersed and dissolved. All other operating parameters remained unchanged. All other steps were the same as in Example 3.
[0159] Comparative Example 9 The proportions of other raw materials and the synthesis process parameters for ZnS / MnS powder all followed those in Example 3; only the components of the compounding control agent were adjusted: dodecyl glucoside was removed, and only KH-550 aminosilane coupling agent was retained, with its dosage being consistent with the effective proportion of KH-550 in the compounding agent in Example 3 (0.088wt%, corresponding to 1 / 4 of the original 0.35wt% compounding agent by mass).
[0160] Synthesis process adjustment: In step S103, only KH-550 aminosilane coupling agent was added, and the mixture was stirred continuously for 22.5 min until completely dispersed and dissolved. All other operating parameters remained unchanged. All other steps were the same as in Example 3.
[0161] Comparative Example 10 The powder synthesis, coating preparation and application, and phosphating solution formulation and preparation S301~S305 are all consistent with Example 3, and the workpiece phosphating time remains unchanged.
[0162] S306 Process Modification: The phosphating tank is completely sealed and enclosed with an opaque light shield to completely isolate the light source. The phosphating process is carried out in the dark throughout, while the operation of the other tank solutions remains unchanged for long-term use.
[0163] Comparative Example 11 The ZnS / MnS powder raw material ratio and synthesis process parameters all follow Example 3; the coating formulation, preparation process, sandblasting coating parameters, and dry film thickness are completely consistent with Example 3.
[0164] Only the sacrificial agent system of the phosphating solution was adjusted: the citric acid component in the original formula was removed and replaced with ascorbic acid as the hole sacrificial agent, while the dosage and ratio of the remaining basic components of the phosphating solution (phosphoric acid, manganese dihydrogen phosphate, manganese nitrate, zinc dihydrogen phosphate, and zinc nitrate) remained the same as in Example 3.
[0165] The raw materials for the phosphating solution, by mass percentage, are: phosphoric acid 45.0%, manganese dihydrogen phosphate 9.75%, manganese nitrate 3.6%, zinc dihydrogen phosphate 5.75%, zinc nitrate 5.25%, ascorbic acid 2.8%, and the remainder is deionized water.
[0166] The preparation steps of phosphating solution S301~S303 are adjusted so that ascorbic acid is added last, and the remaining stirring speed and dissolution time parameters are the same as in Example 3; the phosphating process using S304~S306 is the same as in Example 3.
[0167] Characterization section: The ZnS / MnS powders prepared in the above examples and comparative examples were characterized by electron microscopy and X-ray diffraction (XRD). Metallographic examination was performed on the surface of the phosphated substrate after long-term phosphate treatment. Performance tests were also conducted on the phosphated film and coating of the phosphated coiled steel wire after curing. The relevant characterization and test results are summarized below: (1) X-ray diffraction (XRD) characterization was performed on the ZnS / MnS powders obtained in Example 3 and Comparative Examples 4, 5, 7, 8, and 9. The results are as follows: Figure 1 and Figure 2 As shown.
[0168] X-ray diffraction was used to perform phase identification and crystallographic analysis of the powder. Spectral analysis showed that Example 3 (Zn) 2+ Mn 2+The diffraction peaks of the α-MnS (7:3) can be clearly identified as characteristic peaks of zincblende ZnS (standard card JCPDS No. 05-0566) and α-MnS (standard card JCPDS No. 06-0518). Among them, the characteristic diffraction peaks of zincblende ZnS appear at 2θ=28.5°, 47.5°, and 56.3°, corresponding to its (111), (220), and (311) crystal planes, respectively; the characteristic diffraction peaks of α-MnS appear at 2θ=29.8°, 50.0°, and 58.6°, corresponding to its (111), (220), and (311) crystal planes, respectively. The two-phase diffraction peaks exist independently without significant peak position shift (especially the characteristic peaks at 47.5° and 50.0°, and 56.3° and 58.6° are clearly separated, without merging or broadening), indicating that a homogeneous solid solution was not formed, but rather a heterojunction structure was constructed in the form of a two-phase interface. This structure can form an internal electric field at the interface, effectively driving the spatial separation of photogenerated electron-hole pairs. In Comparative Example 4 (Zn:Mn=9:1), the ZnS diffraction peaks are extremely strong while the MnS characteristic peaks are extremely weak, indicating that the excess Zn leads to insufficient active sites in MnS, a significant reduction in the heterojunction interface area, and insufficient driving force of the internal electric field. In Comparative Example 5 (Zn:Mn=1:1), the MnS diffraction peaks are significantly enhanced, but because the stability of excess MnS is slightly inferior to that of ZnS in weakly acidic hydrothermal treatment and subsequent processing, lattice defects appear on the surface of some particles, the band matching of the heterojunction interface deteriorates, and the recombination rate of photogenerated carriers increases. XRD patterns of Comparative Example 7 (complete removal of the compounding agent), Comparative Example 8 (retention of only dodecyl glucoside), and Comparative Example 9 (retention of only KH-550) show that, due to the lack of steric hindrance and interfacial synergistic control from the complete compounding agent, crystal nucleation and growth during the hydrothermal process are out of control. Zn and Mn elements undergo disordered interdoping in the lattice, and the independent characteristic peaks in the 47°–51° range completely disappear, merging into a single broadened peak. This indicates that it cannot form an independent zincblende type ZnS and α-MnS two-phase structure, but instead forms a (Zn, Mn)S composite phase with high defect states. The homogeneous defect composite phase lacks a clear phase interface and built-in electric field, leading to easy recombination of photogenerated carriers, further confirming the decisive role of specific compounding agents in inducing the construction of a two-phase heterojunction structure. XRD results confirm that a 7:3 molar ratio is the critical optimal range for constructing an efficient and stable built-in electric field in a ZnS / MnS heterojunction.
[0169] (2) The ZnS / MnS powders obtained in Example 3, Comparative Examples 3, and 6-9 were subjected to electron microscopy morphology analysis, and the results are as follows: Figure 3 As shown.
[0170] Field emission scanning electron microscopy was used to observe the morphology of variable-controlled powder samples. The effects of hydrothermal temperature, sulfur source type, and the composition of regulating additives on particle morphology and dispersion performance were systematically analyzed. The sample in Example 3 exhibited a near-spherical nanoparticle morphology with a particle size distribution of 20-30 nm and excellent monodispersity, attributed to the homogeneous slow-release sulfurization mechanism of thioacetamide and the synergistic regulation by dodecyl glucoside and KH-550. In Comparative Example 3, when the hydrothermal temperature was reduced to 100℃, the grain growth kinetics were limited, and the sample exhibited an irregular flocculent morphology with uneven particle size and blurred boundaries, directly confirming that 140-160℃ is a necessary condition for complete grain growth. Comparative Example 6 used sodium sulfide nonahydrate, S... 2- The instantaneous burst release led to uncontrolled homogeneous nucleation, resulting in severe agglomeration of the samples with particle sizes broadened to 50-120 nm, validating the precise control value of the slow-release sulfur source. In Comparative Example 7, after complete removal of the compound control agent, the primary grain size was extremely small with severe lattice distortion, and the particles underwent severe secondary agglomeration, forming micron-sized aggregates. In Comparative Example 8, when only dodecyl glucoside was retained, localized small-scale agglomeration still existed. In Comparative Example 9, when only KH-550 was retained, particle dispersibility improved, but interfacial compatibility was insufficient. The comparison of the three examples confirms that a 3:1 compound of dodecyl glucoside and KH-550 can achieve a synergistic effect of steric dispersion and interfacial modification.
[0171] (3) After phosphating continuously for 72 hours according to all process parameters of Example 3, Comparative Examples 1, 2, 7, 10, and 11, metallographic examination was performed on the inner surface of the substrate in the tank. The results are as follows: Figure 4 As shown.
[0172] To accurately assess the protective effectiveness, the anti-corrosion coating on the surface of the tank substrate was removed before testing, and metallographic testing was performed directly on the exposed substrate. Figure 3The results showed that under continuous 72-hour exposure to strong acid, high temperature, and scouring conditions, the substrate surface of Example 3 showed no corrosion; while the exposed substrates of Comparative Examples 1, 2, 7, 10, and 11 all experienced extremely severe corrosion and deterioration, revealing dense pitting and overall rust, confirming that the coatings in the comparative examples had completely failed, and the acidic medium penetrated directly and eroded the metal substrate. This comparison demonstrates the high synergy of the "photocatalytic self-healing system" of this invention. The absence of any core element will lead to a break in the protective chain: Comparative Examples 1 (no powder) and 10 (light-shielding) resulted in the failure of the photocatalytic triggering mechanism; Comparative Example 2 (no zinc phosphate) lacked a self-healing "ion pool," resulting in the inability of microcracks to heal in situ; Comparative Example 7 (no compounding additives) caused severe powder agglomeration and loss of activity; and Comparative Example 11 (ascorbic acid replacing citric acid) lacked complexing and stabilizing liquid capabilities, leading to bath imbalance and accelerated coating deterioration. In summary, the failure morphology of the substrate after coating removal clearly demonstrates that four key elements are indispensable: effective synthesis of ZnS / MnS photocatalytic powder, zinc phosphate ion pool, photo-triggered reaction, and citric acid complexing agent. This invention is not a conventional physical assembly of components, but rather achieves long-term corrosion protection through multi-mechanism coupling.
[0173] (4) After phosphating according to all process parameters of Example 3 and Comparative Examples 1-11, the surface morphology of the phosphated wire after 72 hours of continuous phosphating was examined by electron microscopy. The results are as follows: Figure 5 As shown.
[0174] The surface morphology of the phosphate film on steel wire was observed using scanning electron microscopy. In Example 3, the phosphate film exhibited uniform grain size, a tightly and orderly arrangement, and no pinholes or loose defects. In Comparative Examples 1 and 10, due to coating corrosion failure and severe corrosion of the substrate, a large amount of iron ions and heavy metal ions such as chromium and cadmium dissolved into the bath, interfering with phosphate crystallization. This resulted in coarse and disordered phosphate film grains with numerous pinholes and pits. In Comparative Example 2, due to the lack of a self-healing zinc phosphate ion pool, the microenvironment of the bath fluctuated, leading to a small number of pinholes on the phosphate film surface. In Comparative Examples 4 and 5, due to the decreased photocatalytic efficiency of the heterojunction, trace amounts of iron ions dissolved, interfering with crystallization kinetics, resulting in slightly uneven phosphate film grain size. In Comparative Examples 3, 6, 7, 8, and 9, due to decreased powder activity and increased iron ion dissolution from the substrate, the phosphate films all exhibited uneven grain size and a loose arrangement. In addition to the corrosion degradation of the coating, Comparative Example 11 also suffered from uncontrolled crystallization of free metal ions in the system due to the lack of complexing and stabilizing function of ascorbic acid, resulting in excessively fine film grains and weak grain boundary bonding. This morphology demonstrates that the system of this invention fundamentally ensures the stability of the phosphating crystallization environment.
[0175] (5) Various performance indicators of the phosphated wires obtained after phosphating for 72 hours in Examples 1-5 and Comparative Examples 1-11 were tested, and the test results are shown in Table 1.
[0176] The specific testing methods and conditions for the performance of the phosphating film in this experiment are as follows: ① Adhesion: Tested according to GB / T 1720-2020 "Paint Film Cross-Cut Test Method"; ② Corrosion resistance: The copper sulfate pitting test method was used. The prepared pitting solution was dropped onto the sample surface and the time when red corrosion spots appeared on the surface was recorded. The pitting solution formula was: 41 g of copper sulfate pentahydrate, 35 g of sodium chloride, 13 mL of 0.1 mol / L hydrochloric acid, and distilled water was added to make up to 1 L. ③ Sodium chloride solution immersion: Immerse the phosphating sample in a 3wt% sodium chloride aqueous solution at room temperature, let it stand for the specified time, and then visually observe whether rust appears on the sample surface. ④ Indoor rust prevention: Place the dried phosphating test piece in a room temperature environment with relative humidity ≤70% and no corrosive gases, and record the time when rust appears on the test piece surface.
[0177] Table 1:
[0178] All phosphating films in the embodiments exhibited a uniform and dense crystalline morphology, achieved an adhesion level of 1, demonstrated corrosion resistance of 78-106s, and provided indoor rust protection for 21-30 days, showing excellent performance. The phosphating films in the 11 comparative examples all showed varying degrees of performance degradation. Comparative Example 1 (no powder) and Comparative Example 10 (light-shielding) showed the worst performance, with adhesion dropping to level 4, corrosion resistance of only 25-27 seconds, and indoor rust prevention for only 3 days. This directly verifies that the photocatalytic mechanism and light conditions are the core prerequisites for the system's protective effectiveness. Comparative Example 2 (without zinc phosphate) showed corrosion resistance dropping to 42 seconds and indoor rust prevention for 8 days, confirming that zinc phosphate is not only a passive rust-preventing pigment but also an indispensable in-situ deposition ion pool in the photocatalytic self-healing mechanism; its absence significantly reduces self-healing ability. Comparative Example 4 (9:1) and Comparative Example 5 (1:1) showed corrosion resistance of 58 seconds and 52 seconds, respectively, and rust prevention for 10-12 days, conversely confirming the effectiveness of zinc phosphate in preventing rust. 2+ Mn 2+The ratio of 7:3 represents a critical optimal solution that balances "photogenerated carrier separation efficiency" and "stability against photocorrosion in strong acid environments," and is not a simple, conventional choice. Comparative Examples 3, 6, 7, 8, and 9, due to insufficient hydrothermal temperature, explosive release of sulfur source, and the absence or reliance on a single regulating agent, resulted in decreased powder activity, corrosion resistance reduced to 32-61 seconds, and rust prevention for 5-14 days, confirming the synergistic necessity of a specific synthesis process and compounded agents. Comparative Example 11 (ascorbic acid substitution) showed corrosion resistance of only 39 seconds and rust prevention for 7 days, confirming the optimal matching degree between citric acid and the system's complexation stabilization and hole sacrificial properties. Overall, the data conversely confirm that the four core elements—ZnS / MnS heterojunction powder (specific molar ratio and process), the zinc phosphate-containing composite filler system, the citric acid-specific sacrificial agent, and the light exposure conditions—work together to ensure the system's long-term corrosion resistance and self-healing efficacy. The absence of any one of these elements leads to a significant reduction in protective performance.
[0179] (6) The coatings obtained in Example 3, Comparative Example 1, and 10 (after complete curing but before contact with phosphating solution) were subjected to conventional performance tests. The test methods are as follows, and the test results are shown in Table 2. ① Coating adhesion: Tested according to GB / T 1720-2020 "Paint Film Cross-Cut Test Method"; ② Impact resistance: Tested according to GB / T 1732-2020 "Test Method for Impact Resistance of Coating Film"; ③ Hardness: Tested according to GB / T 6739-2006 "Determination of Hardness of Paints and Varnishes by Pencil Method"; ④ Flexibility: Tested according to GB / T 1731-2020 "Test Method for Flexibility of Coating Film".
[0180] Table 2:
[0181] In Comparative Examples 1 and 10, without the addition of photocatalytic powder or under no-light conditions, the physical properties of the coatings themselves were basically the same as those in Example 3. The main difference was in the anti-corrosion performance after phosphating.
[0182] The above is a detailed description of the preferred embodiments of the present invention. However, the present invention is not limited to the embodiments described. Those skilled in the art can make various equivalent modifications or substitutions without departing from the spirit of the present invention. All such equivalent modifications or substitutions are included within the scope defined by the claims of the present invention.
Claims
1. A method for preparing ZnS / MnS heterojunction composite photocatalytic powder, characterized in that, Includes the following steps: The composite metal source, the compound regulating agent and the slow-release sulfur source were dissolved in the compound solvent, the pH was adjusted to 5.0-5.4, and the reaction was carried out hydrothermally to obtain ZnS / MnS heterojunction composite photocatalytic powder. By weight percentage, the composite metal source is 5.0%–7.0%, the slow-release sulfur source is 3.8%–6.0%, the compound regulating agent is 0.28%–0.42%, and the balance is the compound solvent; The composite metal source includes soluble zinc salt and soluble manganese salt, the compound regulatory agent includes nonionic biodispersant and silane-modified precursor, and the slow-release sulfur source includes thioacetamide.
2. The method for preparing ZnS / MnS heterojunction composite photocatalytic powder according to claim 1, characterized in that, The soluble zinc salt is zinc acetate dihydrate, and the soluble manganese salt is manganese acetate tetrahydrate; The molar ratio of zinc ions to manganese ions in the composite metal source is (6~8):(4~2); The nonionic dispersant is dodecyl glucoside, and the silane auxiliary is KH-550 aminosilane coupling agent; The mass ratio of nonionic biodispersant to silane-modified precursor is (2~4):1; The pH is adjusted using an aqueous solution of acetic acid; The compound solvents are deionized water and anhydrous ethanol; The volume ratio of deionized water to anhydrous ethanol is (7~9):
1.
3. The method for preparing ZnS / MnS heterojunction composite photocatalytic powder according to claim 2, characterized in that, The molar ratio of zinc ions to manganese ions in the composite metal source is 7:3; The mass ratio of nonionic biodispersant to silane-modified precursor is 3:1; The volume ratio of deionized water to anhydrous ethanol is 9:
1.
4. The method for preparing ZnS / MnS heterojunction composite photocatalytic powder according to claim 1, characterized in that, The hydrothermal reaction temperature is 140–160℃, and the holding time is 10–12 hours. The heating rate of the hydrothermal reaction is 2.5–4 °C; After hydrothermal reaction, the product is cooled, aged, washed, dried, and baked to obtain ZnS / MnS heterojunction composite photocatalytic powder. Cooling was carried out by allowing the vessel to cool naturally to room temperature. The aging process involves natural, static aging for 12–15 hours. The washing process involves alternating between anhydrous ethanol and deionized water. The drying process is vacuum drying, with a temperature of 55–60℃, a time of 9–11 hours, and a vacuum degree of -0.08 to -0.1 MPa. The drying temperature is 210℃~230℃, the time is 2~2.5h, and the atmosphere is nitrogen. Under stirring conditions, the composite metal source, the compound regulating agent and the slow-release sulfur source solution were added to part of the compound solvent in sequence, the pH was adjusted to 5.0-5.4, the remaining compound solvent was added, and a hydrothermal reaction was carried out to obtain ZnS / MnS heterojunction composite photocatalytic powder. The slow-release sulfur source solution is added dropwise over a period of 2–3 hours.
5. ZnS / MnS heterojunction composite photocatalytic powder prepared by the preparation method according to any one of claims 1-4.
6. A photocatalytic self-healing anti-corrosion coating, characterized in that, The product comprises component A and component B. Component A includes fluorine-modified phenolic epoxy resin, the ZnS / MnS heterojunction composite photocatalytic powder as described in claim 5, a composite acid-resistant passivating and rust-preventing filler, a matching compounding agent, and a solvent. Component B includes an acid-resistant low-temperature curing agent and a solvent. Component A and component B are mixed before use. By weight percentage, the photocatalytic self-healing anti-corrosion coating contains 34.0%–36.5% fluorinated modified phenolic epoxy resin, 11.5%–13.5% ZnS / MnS heterojunction composite photocatalytic powder, 18.0%–20.0% composite acid-resistant passivating and rust-preventing filler, 4.2%–4.9% matching compounded additives, 12.0%–14.0% acid-resistant low-temperature curing agent, and the balance being solvent.
7. The photocatalytic self-healing anti-corrosion coating according to claim 6, characterized in that, The mass ratio of solvent in component A to solvent in component B is 7~9:1~3; Composite acid-resistant passivating and rust-preventing fillers include modified aluminum tripolyphosphate, zinc phosphate, glass flakes, and fumed silica; The mass ratio of modified aluminum tripolyphosphate, zinc phosphate, glass flakes and fumed silica is 4~5∶3~4∶3~4∶1; The supporting compounding additives include block polyether dispersants, polysiloxane defoamers, modified acrylic leveling agents, benzotriazole free radical scavengers, and polyamide wax antisettling agents; The mass ratio of block polyether dispersant, polysiloxane defoamer, modified acrylic leveling agent, benzotriazole free radical scavenger, and polyamide wax antisettling agent is 4.0~5.0∶2.0~2.5∶2~2.5∶0.7~0.8∶0.7~0.8; The fluorine content of fluorinated modified phenolic epoxy resin is 10-15 wt%. The fluorine content of the fluorinated modified phenolic epoxy resin is 15 wt%. The acid-resistant low-temperature curing agent is a modified alicyclic amine-phenolic adduct; The amine value of the modified alicyclic amine-phenolic adduct is 380–420 mg KOH / g; The solvent is an environmentally friendly high-boiling-point compound solvent; Environmentally friendly high-boiling-point compound solvents include divalent esters, propylene glycol diacetate, and propylene glycol methyl ether acetate; The mass ratio of divalent ester, propylene glycol diacetate, and propylene glycol methyl ether acetate is 3~4:3~4:3~4.
8. A method for preparing a photocatalytic self-healing anti-corrosion coating, characterized in that, Includes the following steps: (1) Grind, clean, and sandblast the metal substrate, apply primer, and let it dry; (2) Apply the first layer of the photocatalytic self-healing anti-corrosion coating according to any one of claims 6-7, dry, and roughen. (3) Apply a second layer of the photocatalytic self-healing anti-corrosion coating according to any one of claims 6-7, and dry it to obtain a photocatalytic self-healing anti-corrosion coating.
9. The method for preparing the photocatalytic self-healing anti-corrosion coating according to claim 8, characterized in that, Step (1) Sanding involves using coarse sandpaper and fine sandpaper. The coarse sandpaper is 70~80# and the fine sandpaper is 120~130#. Step (1) Cleaning involves rinsing with high-pressure water and then air drying. Step (1) Sandblasting is performed at an air pressure of 0.50-0.60 MPa, with a single-sided area sandblasting speed of 30-45 s / m. 2 ; Step (1) The roughness of the substrate after sandblasting is 60-80 μm; Step (1) Clean the dust after sandblasting; Step (1) The primer is applied in one coat; Step (1) The primer is a thin phosphating passivation primer with a dry film thickness of 15-20 μm; Step (1) Drying is carried out at room temperature for 2-4 hours; Step (2) The dry film thickness of the first layer of photocatalytic self-healing anti-corrosion coating is 80-85 μm; Step (2) Drying involves letting the food stand at room temperature for 6-8 hours, followed by baking at 55-65℃ for 16-20 hours. Step (2) Roughening is done with 300~400# sandpaper; Step (2) Clean the dust after brushing; Step (3) The dry film thickness of the second layer of photocatalytic self-healing anti-corrosion coating is 120-130 μm; Step (3) Drying involves letting the food stand at room temperature for 8-10 hours, followed by baking at 55-65℃ for 24-30 hours.
10. A phosphating tank, characterized in that, The inner wall of the phosphating tank is prepared with a photocatalytic self-healing anti-corrosion coating according to the preparation method described in any one of claims 8-9.
11. A metal phosphating process, characterized in that, A zinc-manganese phosphate solution is added to the phosphate bath described in claim 10, and the metal workpiece is immersed in the zinc-manganese phosphate solution to generate a zinc-manganese composite phosphate film on the surface of the metal workpiece. The inner wall of the phosphating tank is exposed to light; the zinc-manganese phosphating solution contains citric acid.
12. The metal phosphating process according to claim 11, characterized in that, The zinc-manganese phosphating solution is obtained by diluting the mother liquor, which by weight percentage comprises: 43%–47% phosphoric acid, 8.5%–11.0% manganese dihydrogen phosphate, 3.0%–4.2% manganese nitrate, 5.0%–6.5% zinc dihydrogen phosphate, 4.5%–6.0% zinc nitrate, 2.2%–3.2% citric acid, with the remainder being deionized water. The total acidity of zinc-manganese phosphating solution is 25-40 points, and the free acidity is 3-6 points; The temperature of zinc-manganese phosphating solution is 80–85℃; The soaking time is 8-12 minutes; The metal workpiece is a steel workpiece; Metal workpieces undergo degreasing, water washing, rust removal, and neutralization pretreatment; The lighting is either natural light or artificial light.
